Paste for solar cell, solar cell, and method for manufacturing same
By using paste containing organic carriers, mixing copper-containing particles, nanoparticles and metal oxide particles, the problems of high cost of silver materials and easy oxidation of copper materials in solar panels are solved, and the formation of high-efficiency conductive layer and the efficiency of solar panels are achieved. promote.
Patent Information
- Application Number
- CN202411371058.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-12
- Filing Date
- 2020-12-11
- Publication Date
- 2025-02-07
AI Technical Summary
The silver materials used in existing solar panels are costly and difficult to replace, and copper materials are cheap but easily oxidized and diffused, resulting in manufacturing complexity and reduced efficiency.
A paste containing an organic carrier is used to mix copper particles, nanoparticles and metal oxide particles, and the organic carrier is decomposed and reduced by heating to form an efficient conductive layer.
The efficient conductive effect of alternative silver materials is achieved, the production cost is reduced, and the oxidation and diffusion of copper materials is avoided, and the long life and efficiency of solar panels are improved.
Smart Images

Figure CN119403289A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application filed on December 11, 2020, with application number "202080084323.7" and invention title "Paste for Solar Cells, Solar Cells and Methods for Manufacturing the Same".
[0002] Federally funded research
[0003] This invention was made with government support from the National Science Foundation under STTR contract number I-1448883 and SBIR contract number II-1660161, and from the State of Kentucky under STTR contract number KSTC-184-512-15-188 and SBIR contract number 2018-001.
[0004] Cross-references to related applications
[0005] This application claims priority to U.S. Application No. 62 / 947,316, filed December 12, 2019, which is incorporated herein by reference in its entirety. Technical Field
[0006] The present invention generally relates to the manufacture of solar panels and to the composition of pastes used during the manufacture of solar panel components, and more specifically to metal-containing pastes, solar cells made of those pastes, and methods for manufacturing and using those pastes in the manufacture of solar panels. Background Technology
[0007] The solar energy industry has experienced tremendous growth, with an average year-on-year growth rate of approximately 29% over the past decade. In 2018, solar panel manufacturing capacity reached approximately 150 gigawatts. The industry is dominated by crystalline silicon solar cells, with crystalline silicon solar panels accounting for about 95% of the market capacity. However, despite this growth, competitive pricing has led to an 80% drop in the market price of solar panels. Consequently, profit margins have narrowed significantly.
[0008] Although primarily made of silicon, solar panels incorporate many other structural elements to convert sunlight into electricity. A solar panel consists of solar cells, typically connected in series using tabbing wires / ribbons, and hermetically encapsulated between a front and back glass panel. Each solar cell comprises a silicon wafer doped to create a pn junction. When exposed to sunlight, the electric field at the pn junction separates charge carriers (i.e., electrons and holes). This generates an electric current.
[0009] Other structural features of solar panels may include an anti-reflective coating (e.g., silicon nitride (SiN) and titanium dioxide (TiO2)) on the front or sun-exposed side of the doped silicon wafer. The coating reduces light reflection from the cell and thus improves cell efficiency. Charge carriers generated during light exposure are collected by conductive contacts on the front and back of each cell. These conductive contacts are typically positioned as lines 15 μm to 200 μm wide across the entire front side, spaced 0.7 mm to 5 mm apart. Each line can be referred to as a “finger.” The spacing and individual width of the fingers allow sunlight to reach a large surface area of the doped silicon. The conductive contacts on the back side do not need to be transparent. Typically, a thin metal layer (e.g., aluminum) forms the back of the cell. Additional conductive connectors (e.g., 0.1 mm to 2 mm wide busbars made of silver) are electrically coupled to the fingers and the aluminum back side. While not limited to any particular number, the number of busbars can be 2 to 8 and can be replaced with other configurations or even non-busbar designs.
[0010] Currently, the fingers and buses on silicon solar cells are almost entirely made of silver (Ag). With increasing demand and plummeting reserves, manufacturers have minimized silver usage. This minimization has been achieved through improved paste formulations and optimized paste printing processes. One way to reduce costs is to reduce the width of each silver finger. This alone has resulted in a 50% reduction in silver consumption. While further reductions are possible, there is a lower limit below which device performance and production yields become unacceptable. As manufacturers push the lower limit of silver usage to reduce costs, cheaper silver alternatives are being investigated.
[0011] Copper is an ideal substitute for silver. It is much cheaper and has similar electrical conductivity. However, a drawback is that copper causes rapid degradation in solar cells, thus complicating manufacturing. To address the degradation problem, particularly the diffusion of copper into silicon, different techniques can be used to deposit copper on silicon. One technique is electroplating. While generally successful, electroplating requires newer equipment and additional processing beyond current silver paste screen printing techniques. Because electroplating with copper requires significant capital investment, it has not yet been adopted industrially. Other disadvantages also exist.
[0012] Electroplating copper requires applying a diffusion barrier layer to silicon before copper deposition. Copper is then electroplated onto this barrier layer. Thus, the diffusion barrier layer separates the copper from the silicon. During solar cell use, the barrier layer prevents copper from diffusing into the silicon. Another issue is that, unlike silver, copper is prone to oxidation.
[0013] Once oxidized, copper's adhesion to the diffusion barrier layer and its solderability are negatively affected. Soldering other electrical connections to the fingers then becomes problematic. To minimize oxidation, a tin or silver overlay is applied to the copper. This complex multilayer structure requires significant capital expenditure and multiple separate deposition processes. These additional layers and processes negate any material cost advantages of using copper. Furthermore, the plating bath introduces environmental, health, and safety issues. Ultimately, the material cost savings from using copper are masked by the high capital and production costs.
[0014] To address these and other issues, what is needed in the field is a replacement for silver in solar panels. More specifically, manufacturers are seeking solutions to the problems arising from using copper instead of silver. Summary of the Invention
[0015] This invention overcomes the aforementioned and other shortcomings and disadvantages of solar panels, pastes, and methods for manufacturing them. While the invention will be described in conjunction with certain embodiments, it should be understood that the invention is not limited to these embodiments. Rather, the invention includes all alternatives, modifications, and equivalents that may be included within the spirit and scope of the invention.
[0016] According to the principles of the present invention, a paste for metallizing a solar cell comprises an organic carrier and a mixture of copper-containing particles, metal-oxide-containing nanoparticles, and second oxide particles different from the metal-oxide-containing nanoparticles within the organic carrier. The second oxide particles comprise metal oxide particles, and when the paste is heated to a temperature at which the organic carrier decomposes, the metal of the metal oxide is capable of reducing at least some of the metal-oxide-containing nanoparticles to metal.
[0017] In one embodiment, the organic carrier can reduce the metal oxide of the second oxide particles via decomposition.
[0018] In one embodiment, the organic carrier comprises polyvinylpyrrolidone.
[0019] In one embodiment, the second oxide particles comprise glass frit particles.
[0020] In one embodiment, the copper-containing particles include metallic copper particles or copper alloy particles.
[0021] In one embodiment, the copper particles have at least one metal selected from nickel, cobalt, or manganese on their surface or on the surface of the copper alloy particles.
[0022] In one embodiment, at least one of the metals selected from nickel, cobalt, or manganese is in the form of metal particles on the surface of the copper particles or on the surface of the copper alloy particles.
[0023] In one embodiment, at least one of the metals selected from nickel, cobalt, or manganese is in the form of metal oxide particles on the surface of the copper particles or on the surface of the copper alloy particles.
[0024] In one embodiment, the copper particles or the copper alloy particles and / or the at least one metal are doped with at least phosphorus.
[0025] In one embodiment, the surface of the copper particles or the surface of the copper alloy particles is not completely covered by the at least one metal.
[0026] In one embodiment, the at least one metal covers at least a portion of the surface of the copper particles or at least a portion of the surface of the copper alloy particles.
[0027] In one embodiment, the metal oxide of the second oxide particle is an antimony oxide.
[0028] In one embodiment, the metal-oxide-containing nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.
[0029] In one embodiment, the metal-oxide-containing nanoparticles include nickel oxide and lead oxide.
[0030] In one embodiment, the metal oxide of the second oxide particle includes antimony oxide.
[0031] In one embodiment, the metal-oxide-containing nanoparticles include nickel oxide, copper oxide, and lead oxide.
[0032] In one embodiment, the paste is silver-free.
[0033] In one embodiment, the ratio of the second oxide particles to the metal-oxide-containing nanoparticles is in the range of 0.50 to 16.96 by weight.
[0034] In one embodiment, the ratio of the second oxide particles to the metal-oxide-containing nanoparticles is in the range of 1.50 to 3.51 by weight.
[0035] In one embodiment, at least one metal selected from nickel, cobalt, and manganese is in the form of metal particles on the surface of the copper-containing particles, and the surface area of the copper-containing particles having the metal particles is 1m². 2 / g to 5m2 Within the range of / g.
[0036] In one embodiment, at least one metal selected from nickel, cobalt, and manganese is in the form of metal particles on the surface of the copper-containing particles, and the surface area of the copper-containing particles having the metal particles is 0.7 m². 2 / g to 5m 2 Within the range of / g.
[0037] In one embodiment, the copper-containing particles comprise a mixture of fine copper powder and coarse copper powder.
[0038] In one embodiment, the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm, and the coarse copper powder is characterized by an average particle size in the range of 7.53 μm to 14.69 μm, 10 μm to 20 μm, or 1.75 μm to 7.20 μm.
[0039] In one embodiment, the organic carrier is an organic adhesive and an organic solvent.
[0040] In one embodiment, the organic carrier further comprises a viscosity modifier.
[0041] In one embodiment, the organic solvent is propylene glycol.
[0042] In one embodiment, the organic carrier further comprises an organic adhesive.
[0043] According to the principles of the present invention, the paste comprises a mixture of an organic carrier and particles within the organic carrier, said particles including metallic copper particles, nanoparticles, and metal oxide particles. The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide, and lead oxide.
[0044] In one embodiment, the metal oxide of the metal oxide particles has a more negative Gibbs free energy of formation than the metal oxide of at least one oxide in the nanoparticles.
[0045] In one embodiment, the copper particles form the largest volume portion of the metal in the paste.
[0046] In one embodiment, the nanoparticles include particles containing lead oxide.
[0047] In one embodiment, the nanoparticles are nickel oxide and lead oxide.
[0048] In one embodiment, the metal oxide particles comprise particles of antimony oxide.
[0049] In one embodiment, the nanoparticles include particles comprising lead oxide and the metal oxide particles comprising antimony oxide.
[0050] In one embodiment, the organic carrier can reduce the metal oxide particles via decomposition.
[0051] In one embodiment, the organic carrier comprises polyvinylpyrrolidone.
[0052] In one embodiment, the metal oxide particles comprise glass frit particles.
[0053] In one embodiment, the copper particles have at least one metal selected from nickel, cobalt, or manganese on their surface.
[0054] In one embodiment, at least one of the metals selected from nickel, cobalt, or manganese is in the form of metal particles on the surface of the copper particles.
[0055] In one embodiment, at least one of the metals selected from nickel, cobalt, or manganese is in the form of metal oxide particles on the surface of the copper particles.
[0056] In one embodiment, the copper particles and / or the at least one metal are doped with at least phosphorus.
[0057] In one embodiment, the surface of the copper particles is not completely covered by the at least one metal.
[0058] In one embodiment, the at least one metal covers at least a portion of the surface of the copper particles.
[0059] In one embodiment, the metal oxide particles are particles of antimony oxide.
[0060] In one embodiment, the nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.
[0061] In one embodiment, the nanoparticles comprise nickel oxide and lead oxide.
[0062] In one embodiment, the metal oxide particles are particles of antimony oxide.
[0063] In one embodiment, the nanoparticles include nickel oxide, copper oxide, and lead oxide.
[0064] In one embodiment, the paste is silver-free.
[0065] In one embodiment, the ratio of metal oxide particles to nanoparticles is in the range of 0.5 to 17 by weight.
[0066] In one embodiment, the ratio of metal oxide particles to nanoparticles is in the range of 1.5 to 3.5 by weight.
[0067] In one embodiment, the ratio of metal oxide particles to nanoparticles is in the range of 0.25 to 20 by weight.
[0068] In one embodiment, the ratio of metal oxide particles to nanoparticles is in the range of 3 to 17 by weight.
[0069] In one embodiment, the nanoparticles include particles containing lead oxide and / or lead hydroxide, and the metal oxide particles include particles containing antimony oxide.
[0070] In one embodiment, the copper particles are modified to include metal-containing particles on their surface.
[0071] In one implementation, the surface area of the modified copper particles is greater than that of the unmodified copper particles.
[0072] In one embodiment, the surface area of the modified metallic copper particles is 0.7 m². 2 / g to 5m 2 Within the range of / g.
[0073] In one embodiment, the surface area of the modified metallic copper particles is 1m². 2 / g to 5m 2 Within the range of / g.
[0074] In one embodiment, the copper particles comprise a mixture of fine copper powder and coarse copper powder.
[0075] In one embodiment, the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm, and the coarse copper powder is characterized by an average particle size in the range of 7.53 μm to 14.69 μm, 10 μm to 20 μm, or 1.75 μm to 7.20 μm.
[0076] In one embodiment, the organic carrier is an organic adhesive and an organic solvent.
[0077] In one embodiment, the organic carrier further comprises a viscosity modifier.
[0078] In one embodiment, the organic solvent is propylene glycol.
[0079] In one embodiment, the organic carrier further comprises an organic adhesive.
[0080] In one embodiment, the organic solvent is one of propylene glycol, dipropylene glycol, and tripropylene glycol, or a combination thereof.
[0081] In one embodiment, the metallic copper particles are composed of fine copper powder. In one embodiment, the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm.
[0082] According to the principles of the present invention, the paste is essentially composed of an organic carrier and a mixture of metallic copper particles, nanoparticles, and metal oxide particles within the organic carrier. The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide, and lead oxide.
[0083] According to the principles of the present invention, the paste comprises an organic carrier and a mixture of copper particles, nanoparticles, and metal oxide particles within the organic carrier. The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide, and lead oxide.
[0084] According to the principles of the present invention, a solar cell includes a semiconductor substrate and at least one copper-containing conductor on the semiconductor substrate. The copper-containing conductor comprises a plurality of grains of copper or a copper alloy, and at least a portion of the grain boundaries between adjacent grains comprises at least one of lead, copper, cobalt, manganese, tellurium, and bismuth, and at least one other metal.
[0085] In one embodiment, the oxide of at least one other metal has a more negative Gibbs free energy of formation than the lead oxide.
[0086] In one embodiment, the at least one other metal is antimony.
[0087] In one embodiment, at least a portion of the grain boundary further comprises nickel.
[0088] In one embodiment, the copper-containing conductor and the semiconductor substrate meet at an interface, and the interface comprises lead and the at least one other metal between the semiconductor substrate and the grain.
[0089] In one embodiment, the interface comprises a metal silicide.
[0090] In one embodiment, the interface also contains nickel.
[0091] In one embodiment, the solar cell does not contain silver.
[0092] In one embodiment, the copper-containing conductor is a finger-like object.
[0093] In one embodiment, the thickness of the fingers is in the range of 10 μm to 100 μm.
[0094] In one embodiment, the solar cell includes a highly doped silicon emitter layer and the fingers making electrical contact with the silicon emitter layer.
[0095] In one embodiment, the resistivity of the fingers is in the range of 2 to 10 times that of bulk copper.
[0096] In one implementation, the conductor is a bus.
[0097] In one embodiment, the thickness of the busbar is in the range of 10 μm to 100 μm.
[0098] In one embodiment, the solar cell includes an anti-reflective layer on the semiconductor substrate, the anti-reflective layer defining an outer surface of the solar cell, and the busbar being in direct contact with the anti-reflective layer but not with the semiconductor substrate.
[0099] In one embodiment, the solar cell further includes a plurality of buses arranged in a pattern in which the buses are spaced apart at a distance of less than 40 mm.
[0100] In one embodiment, the solar cell does not have a separately deposited diffusion barrier layer between the copper conductor and the semiconductor substrate.
[0101] According to the principles of the present invention, a method for manufacturing a solar cell includes: placing a paste on the surface of a substrate, the paste comprising an organic carrier and a mixture of particles within the organic carrier, the particles comprising copper particles, nanoparticles, and metal oxide particles. The nanoparticles comprise at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide. The paste is then heated to a temperature at which the organic carrier decomposes and at least some of the metal oxides are reduced to metals.
[0102] In one implementation, heating includes heating in the air.
[0103] In one embodiment, during heating, the metal reduces at least some of the metal-oxide-containing nanoparticles to metal.
[0104] In one embodiment, the substrate includes a silicon nitride layer, and during heating, heated metal oxides and metals react with the silicon nitride layer.
[0105] According to the principles of the present invention, a method for modifying the surface of copper-containing particles for use in a paste includes mixing copper-containing particles with metal ions in a solution, adding a reducing agent to the mixture of copper-containing particles and metal ions to reduce the metal ions to metal, such that the metal is deposited on the surface of the copper-containing particles, and separating the surface-modified copper-containing particles from the solution.
[0106] In one embodiment, the method further includes heating a mixture containing copper particles, metal ions, and a reducing agent.
[0107] In one embodiment, the surface-modified copper-containing particles have a larger surface area than the copper particles before the metal was deposited.
[0108] In one embodiment, the surface-modified copper-containing particles have a surface area of at least 0.66 m². 2 / g.
[0109] In one embodiment, the surface-modified copper-containing particles have a surface area of at least 0.83 m². 2 / g.
[0110] In one embodiment, the metal ion is one or more of nickel, manganese, and cobalt. One embodiment includes a paste comprising surface-modified copper-containing particles.
[0111] According to the principles of the present invention, a method for preparing a paste for metallizing solar cells includes mixing a plurality of particles together in an organic carrier. The plurality of particles includes copper-containing particles, nanoparticles, and second oxide particles.
[0112] In one embodiment, prior to mixing, the method further includes modifying the surface of the copper-containing particles to increase the surface area of the copper-containing particles by at least 20%.
[0113] In one embodiment, prior to mixing, the method further includes modifying the surface of the copper-containing particles by exposing the copper-containing particles to a solution and depositing particles of metal and / or metal oxides on the surface of the copper-containing particles.
[0114] In one embodiment, prior to mixing, the method further includes mixing a first powder containing the copper-containing particles with a second powder containing the copper-containing particles, the first powder being characterized by a first average particle size and a first particle size distribution, and the second powder being characterized by a second average particle size and a second particle size distribution, the first average particle size being larger than the second average particle size.
[0115] In one implementation, all copper-containing particles originate from a single particle size distribution.
[0116] In one embodiment, the mixing includes mixing at least 80% by weight of the copper-containing particles, 1% to 15% by weight of the second oxide particles, and 1% to 10% by weight of the nanoparticles with 1% to 13% by weight of the organic carrier.
[0117] In one embodiment, mixing includes mixing copper particles, nanoparticles containing at least lead, and antimony oxide particles together.
[0118] In one embodiment, prior to mixing, the method further includes modifying the surface of the copper-containing particles to increase the surface area of the copper-containing particles by at least 2%.
[0119] In one embodiment, the copper-containing particles consist of fine copper powder.
[0120] In one embodiment, the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm.
[0121] In one embodiment, the ratio of the second oxide particles to the metal-oxide-containing nanoparticles is in the range of 0.25 to 20 by weight.
[0122] In one embodiment, the ratio of the second oxide particles to the metal-oxide-containing nanoparticles is in the range of 3 to 17 by weight. Attached Figure Description
[0123] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate some embodiments of the invention and, together with the detailed description given below, serve to explain various aspects of the invention.
[0124] Figure 1 This is a plan view of a solar panel cell array according to one embodiment of the present invention.
[0125] Figure 2 This is according to one embodiment of the present invention. Figure 1 An enlarged plan view of one of the solar cells in the solar panel shown.
[0126] Figure 3 yes Figure 2 An enlarged perspective cross-sectional view of the solar cell taken along section line 3-3.
[0127] Figure 4 This is a schematic diagram of a cross-section of a paste line on a substrate according to an embodiment of the present invention.
[0128] Figure 5 This is according to one embodiment of the present invention. Figure 4A schematic diagram of the cross-section of the paste line after drying.
[0129] Figure 6 Is Figure 5 A schematic diagram of the cross-section of the wire after it has been fired.
[0130] Figure 7A and Figure 7B This is a flowchart illustrating the manufacture of exemplary nanoparticles according to an embodiment of the present invention.
[0131] Figure 8 TEM images of particles with an overlaid layer, manufactured according to one embodiment of the present invention, are shown.
[0132] Figure 9A This is a flowchart of a process for surface modification of copper-containing particles prior to their use in a paste, according to one embodiment of the present invention.
[0133] Figure 9B This is a flowchart for paste preparation according to one embodiment of the present invention.
[0134] Figure 10 This is a graph showing the temperature profile of the reaction mixture according to an exemplary process for surface modification of copper-containing particles according to one embodiment.
[0135] Figure 11A , Figure 11B , Figure 11C and Figure 11D These are the normalized short-circuit current densities (J / L) of the paste prepared without surface modification of the copper-containing particles. sc Normalized open-circuit voltage (V) oc Accelerated aging test plots of normalized fill factor (FF) and normalized efficiency (η).
[0136] Figure 12A It is the normalized open-circuit voltage (V) of pastes prepared using different implementation schemes of nanoparticles and fired at different temperatures. oc The accelerated aging test chart.
[0137] Figure 12B , Figure 12C , Figure 12D and Figure 12E This is a graph showing the effect of accelerated aging tests on the PV performance of pastes prepared using different implementation schemes of nanoparticles and fired at different temperatures.
[0138] Figure 12F and Figure 12G It is the normalized open-circuit voltage (V) of pastes prepared using different implementation schemes of nanoparticles and fired at different temperatures. oc) and normalized short-circuit current density (J sc The accelerated aging test diagram.
[0139] Figure 12H and Figure 12I This is an accelerated aging test graph showing the normalized filler factor (FF) and normalized efficiency (η) of pastes prepared using different implementation schemes of nanoparticles and fired at different temperatures.
[0140] Figure 13A , Figure 13B , Figure 13C and Figure 13D Normalized short-circuit current density (J) of exemplary embodiments of pastes on batteries from different manufacturers sc ), Normalized fill factor (FF), Normalized open-circuit voltage (V) oc A graph of ) and normalized efficiency (η).
[0141] Figure 13E , Figure 13F , Figure 13G and Figure 13H This is a current-voltage graph after accelerated aging testing of exemplary embodiments of paste on batteries from different manufacturers.
[0142] Figure 14A , Figure 14B and Figure 14C This is an accelerated aging current-to-voltage graph of an exemplary battery made from a paste containing increased amounts of second oxide and nanoparticles.
[0143] Figure 15A , Figure 15B , Figure 15C , Figure 15D and Figure 15E The normalized short-circuit current density (J / L) of different embodiments of the paste containing an increased ratio of second oxide to nanoparticles are respectively. sc Normalized open-circuit voltage (V) oc Accelerated aging test graphs for normalized fill factor (FF), normalized efficiency (η), and normalized resistance. Figure 15F This is an accelerated aging test graph of normalized FF as the second oxide in the paste changes relative to the nanoparticles.
[0144] Figure 16A , Figure 16B , Figure 16C , Figure 16D and Figure 16E These are the normalized short-circuit current densities (J / L) of exemplary embodiments using pastes containing copper particles with increased surface modification. sc Normalized open-circuit voltage (V) ocAccelerated aging test graphs for normalized fill factor (FF), normalized efficiency (η), and normalized resistance.
[0145] Figure 17A , Figure 17B , Figure 17C and Figure 17D This is a current density versus voltage graph of exemplary batteries made from different pastes after accelerated aging tests, wherein the pastes use copper-containing particles with increased surface modification.
[0146] Figure 18A , Figure 18B and Figure 18C This is a graph showing the effect of changing the ratio of two copper-containing particles with different particle size ranges on the surface area, volume, and weight contributions of the total copper load in the paste, while keeping the total surface area contribution of copper-containing particles constant.
[0147] Figure 18D and Figure 18E Optical microscopic images of pastes made with 100% coarse (10 μm to 22 μm) copper particles and 100% fine (1.2 μm to 3.2 μm) copper particles, respectively.
[0148] Figure 19A and Figure 19B This is a graph illustrating the effect of the ratio of coarse to fine copper particles in the paste on the resistivity of the contact material formed after firing.
[0149] Figure 20A and Figure 20B This is a graph showing the current density relative to voltage for paste embodiments using different ratios of coarse copper particles and fine copper particles.
[0150] Figure 20C This is a graph showing the axial velocity relative viscosity of two exemplary pastes made using surface-modified copper-containing particles with different particle shapes.
[0151] Figure 20D and Figure 20E This is a cross-sectional SEM micrograph of an exemplary paste made from copper-containing powder with different particle shapes after firing.
[0152] Figure 21A , Figure 21B and Figure 21C These are optical images of pastes prepared by varying the ratio of coarse to fine copper particles to 100:0, 90:10, and 80:30 after firing.
[0153] Figure 22 This is a cross-sectional SEM image of a fired finger made from pastes prepared using various implementation schemes.
[0154] Figure 23 It is an X-ray diffraction pattern of a film made using nanoparticles according to an embodiment of the present invention, which has been deposited and heat-treated.
[0155] Figure 24A and Figure 24B This is a current density relative to voltage diagram, showing the effect of increasing the amount of organic carrier and changing the firing temperature on the battery electrical characteristics in some implementations of the paste.
[0156] Figure 25A , Figure 25B , Figure 25C , Figure 25D , Figure 25E and Figure 25F The figures show the bulk resistivity, contact resistivity, and J of the second oxide and nanoparticles, respectively. sc FF, V oc Interaction diagram of the design of experiment (DOE) for the interaction between η and η.
[0157] Figure 26A and Figure 26B The images shown are SEM images and images illustrating the microstructure formed after firing a paste containing a high proportion of the second oxide.
[0158] Figure 27A , Figure 27B and Figure 27C The image shows a cross-sectional SEM image of a finger printed with an exemplary paste containing different ratios of coarse, medium, small, and fine copper powders.
[0159] Figure 28A and Figure 28B These are optical images of the front and back sides of a printed article made with an exemplary paste formulated to have low porosity.
[0160] Figure 29A , Figure 29B , Figure 29C , Figure 29D and Figure 29E It is a voltage-to-current density plot of a paste containing an increased amount of the second oxide.
[0161] Figure 30A , Figure 30B , Figure 30C , Figure 30D and Figure 30E Normalized short-circuit current density (J) of an exemplary paste with increased firing time. sc ), normalized fill factor (FF), open-circuit voltage (V) oc Accelerated aging test graphs for normalized efficiency (η) and normalized resistance.
[0162] Figure 30F , Figure 30G and Figure 30H This is a graph of current density relative to voltage in an accelerated aging test of an exemplary paste with increased firing time.
[0163] Figure 31A , Figure 31B , Figure 31C , Figure 31D , Figure 31E The figures show that when the surface area of the surface-modified fine copper-containing particles in the paste is 1.10 m², the results are shown. 2 At / g, the amount of organic carrier in the paste and the firing conditions (i.e., holding time) affect J sc V oc The effects of FF, η, and the resistance of the entire finger.
[0164] Figure 31F , Figure 31G , Figure 31H , Figure 31I , Figure 31J The figures show that when the surface area of the surface-modified fine copper-containing particles in the paste is 2.65 m², the results are as follows: 2 At / g, the amount of organic carrier in the paste and the firing conditions (i.e., holding time) affect J sc V oc The effects of FF, η, and the resistance of the entire finger.
[0165] Figure 31K , Figure 31L , Figure 31M , Figure 31N , Figure 31O The figures show that when the surface area of the surface-modified fine copper-containing particles in the paste is 2.65 m², the results are as follows: 2 At / g, the amount of organic carrier in the paste and the firing conditions (i.e., holding time) affect J sc V oc The effects of FF, η, and the resistance of the entire finger.
[0166] Figure 32A , Figure 32B , Figure 32C , Figure 32D , Figure 32E and Figure 32F These are optical microscope images of the finger-shaped objects after firing, in which... Figure 32A No nanoparticles Figure 32B The ratio of the second oxide to nanoparticles is 16.75. Figure 32C The ratio of the second oxide to nanoparticles is 8.37. Figure 32D The ratio of the second oxide to nanoparticles is 5.58. Figure 32EThe ratio of the second oxide to nanoparticles is 4.19. Figure 32F The ratio of the second oxide to nanoparticles is 3.35.
[0167] Figure 33A and Figure 33B The effect of increasing the amount of glass frit in the paste on PV performance (fill factor, FF) is shown as a contribution to the usable surface area of (a) approximately 0.80 m². 2 / gram of paste and (b) 0.57m 2 / gram of paste is a function of the printing weight of the paste made from copper-containing powder.
[0168] Figure 34A , Figure 34B , Figure 34C and Figure 34D The PV performance (respectively) is shown. Figure 34A Short-circuit current density, Figure 34B Open circuit voltage, Figure 34C Fill factor and Figure 34D Efficiency is a function of the belt speed used to fire batteries in an industrial IR belt furnace.
[0169] Figure 35 The current-voltage (IV) curves of the paste, made using only fine copper-containing powders ranging from 1.2 μm to 3.2 μm, are shown under both dark and light conditions.
[0170] Figure 36A , Figure 36B and Figure 36C The use of copper-containing particles with the following surface area to measure the open-circuit voltage V is shown. oc Impact: Figure 36A 0.51m 2 / gram of paste, Figure 36B 0.57m 2 / gram of paste, Figure 36C 0.65m 2 / gram of paste.
[0171] Figure 37A and Figure 37B The effect of accelerated aging tests at 200°C on PV performance (using CuBert) is shown. TM Polycrystalline Si solar cells with all-Al BSF back contacts metallized from paste Figure 37A Open circuit voltage and Figure 37B The influence of pseudo-filling factor.
[0172] Figure 38A and Figure 38BThe efficiency of monocrystalline silicon PERC solar cells printed using pastes made from standard Ni / Ni / Pb nanoparticles with Ni / Pb ratios of 1.52 and 0.52 is shown. The effect of doubling the proportion of nanoparticles and the amount of binder on PV performance is also shown.
[0173] Figure 39A , Figure 39B and Figure 39C The firing conditions shown affect the use of binders containing 2.05 wt% of binder in Figure 39A, 2.35 wt% of binder in Figure 39B, and... Figure 39C The effect of 2.64% by weight of the adhesive paste on the resistance of the entire 22 fingers with a length of 3.2 mm printed on them.
[0174] Figure 40 It is an optical micrograph of a finger based on an example.
[0175] Figure 41A and Figure 41B It is an optical microscope image of a finger printed with two different screen sizes before firing, based on an example. Detailed Implementation
[0176] Reference Figure 1 and Figure 2 The solar panel (not shown) battery array 10 includes a plurality of solar cells 12. Although Figure 1 Although not shown, the cell array 10 may be an assembly package including a front panel, a rear panel, and a sealant layer (e.g., ethylene vinyl acetate). A silicon substrate lies between the sealant layers and the front and rear panels. Interconnectors are required to electrically connect the cells 12 within the array 10. These components may be enclosed within a frame (not shown). The number of cells 12 within the array 10 may differ from that shown. For example, a solar panel may include sixty or more cells. Other common cell counts are 72 and 90. However, embodiments of the invention are not limited to any number of solar cells 12 in the cell array 10.
[0177] As described herein, one or more of the cells 12 may include one or more copper-containing electrical conductors (i.e., electrodes). The majority of the metallic conductors may be copper, with the remainder being other metals and / or metallic materials. In one embodiment, one or more of the solar cells 12 are silver-free. Advantageously, the solar cells 12 can be produced cost-effectively because the copper-containing conductors replace the silver conductors. Furthermore, as described herein, the copper-containing conductors are produced from a copper-containing paste during the metallization process. As another advantage, the paste of the present invention can replace processes currently using silver-containing pastes, such as in solar cell / panel manufacturing processes. As will be understood, this eliminates the necessity of the substantial capital investment observed with copper plating techniques while providing a cost-effective method for producing solar cells that primarily have copper electrodes and in which silver is absent.
[0178] Reference Figure 2 and Figure 3 The solar cell 12 includes a semiconductor substrate or wafer 14. Wafer 14 is monocrystalline silicon. However, embodiments of the present invention are also applicable to polycrystalline silicon substrates and other semiconductor substrates and films. See also... Figure 3 The wafer 14 may include an n-type doped silicon region 16 adjacent to the p-type doped silicon region 18 to form a pn junction. Other architectures may include inversion of p and n doped regions and combination of locally doped regions. When silicon is bombarded by photons of light, the combination of regions 16 and 18 allows electrons to separate from holes. An anti-reflective coating 20 covers the n-type doped silicon region 16 and defines the front surface 22 of the solar cell 12. For example, the anti-reflective coating 20 may be silicon nitride (SiN). The anti-reflective coating 20 reduces the amount of incident light (by photons of light)... Figure 3 (Indicated by arrow 24) The amount of reflection from the front surface 22 increases the portion of incident light 24 that impacts the wafer 14. The anti-reflective coating 20 also helps passivate the surface of the silicon wafer 14, which reduces recombination losses. This improves the electrical efficiency of the solar cell 12.
[0179] A plurality of electrical conductors 26, called fingers, are exposed on the front surface 22 of the solar cell 12. For example... Figure 3As shown, the fingers 26 penetrate the anti-reflective coating 20 and make electrical contact with the wafer 14, particularly with the n-type doped silicon region 16. The back conductor 30 makes electrical contact with the p-type doped region 18 of the wafer 14, opposite to the fingers 26. Conductors 26 and 30 conduct current generated by photons of light striking the wafer 14 to ultimately generate electricity. According to embodiments of the invention, one or more of the fingers 26 and / or the back conductor 30 may be copper-containing and may also be silver-free in this respect. The fingers 26, manufactured as described herein, have a conductivity that is 2 to 10 times lower than that of bulk metallic copper. The resistivity of the fingers is the reciprocal of their conductivity. The back conductor 30 may be formed of aluminum or another electrical conductor, with a thickness ranging from 10 μm to 100 μm. As mentioned above, for example, the fingers 26 may be formed of a copper-containing paste, and thus replace a silver-containing paste in the manufacture of the solar cell 12.
[0180] In this regard and now refer to Figure 4 , Figure 5 and Figure 6 According to one embodiment of the present invention, a copper-containing paste 32 (shown in...) Figure 4 The anti-reflective coating 20 and the wafer 14 are placed on the front surface 22 of the substrate 40. The copper-containing paste 32 can be screen-printed onto the substrate 40 or applied by another method. As shown, the substrate 40 includes an anti-reflective coating 20 and a wafer 14. In the case where the back conductor 30 is made of aluminum, it may already be present (as shown) or may be formed during the production of the fingers 26. During manufacturing, the substrate 40, the anti-reflective coating 20, the wafer 14, the back conductor 30, and the paste 32 are used or deposited to produce the product. Figure 2 Battery 12 is shown.
[0181] During printing on substrate 40, refer to Figure 4 A copper-containing paste 32 defines elongated bodies (e.g., lines) with height, width, and length on a substrate 40. As described below, the elongated bodies transform into fingers during the firing of the paste 32. For this purpose, the paste 32 contains a plurality of particles 42 contained in an organic carrier 44. The rheological properties of the paste 32 can be adjusted by changing the composition of the organic carrier 44 and / or the particles 42 to allow the paste 32 to be dispensed via a screen printing process (e.g., a process similar to that used for screen printing silver-containing pastes on silicon wafers) or by another method. The rheological properties of the paste 32 are sufficient to allow the paste 32 to be dispensed while also allowing the paste 32 to maintain the dispensed pattern and not diffuse across the entire substrate 40; thereby allowing the fingers to maintain a high aspect ratio (finger height / finger width).
[0182] By way of example only and not limitation, the organic carrier 44 may be a mixture of an organic adhesive and one or more solvents, dispersants, viscosity modifiers, and / or surface tension modifiers. Exemplary adhesives include polyvinylpyrrolidone (PVP), ethyl cellulose, and monosaccharides such as fructose. Exemplary solvents, in addition to water, include alcohols, ester alcohols, and glycols such as propylene glycol, ethylene glycol, polyethylene glycol, and texanol. TM Ester alcohols, as well as ether alcohols and diols, such as diethylene glycol and triethylene glycol. Exemplary viscosity and surface tension modifiers include... 111、 180. 190. RE-610 and sodium stearate, to name just a few. The volume of the organic carrier 44 and the proportion of each type of particle 42 in the paste 32 can be adjusted to meet desired rheological (e.g., viscosity) specifications. Typically, the paste 32 may contain only a few weight percent of the organic carrier 44. For example, the paste 32 contains organic carrier 44 in the range of 1 wt% to 15 wt%.
[0183] The copper-containing paste 32 is a mixture of particles with different compositions. That is, the paste 32 can be a powder mixture that provides all the particles 42. Each powder may include particles 42 with different compositions, particle sizes and / or particle shapes.
[0184] In one embodiment, the copper-containing paste 32 comprises a plurality of copper-containing particles 46 forming the largest volume portion of particles 42 in the paste 32. The copper-containing particles 46 can form the majority of the volume of fingers 26. After firing, by virtue of the composition of the particles 42, the fingers 26 are able to provide conductivity sufficient to promote effective solar cell performance through metallic copper or copper-containing metals. For example, the copper-containing particles 46 can be metallic copper and form 48% to 88% of the solids in the paste 32. This can be converted to at least 80% by weight of copper metal in the paste 32 before drying. The range of copper metal in the paste 32 can be 62% to 98% by weight. Although the copper-containing particles 46 are described with reference to metallic copper, the copper-containing particles 46 are not limited to metallic copper and may contain small amounts of impurity elements. The copper-containing particles 46 can be copper alloy particles or copper-containing nonmetallic (e.g., oxide) particles that can be reduced to copper or copper alloys. Copper alloys are alloys containing copper as their main component, such as bronze (copper-tin alloy) and brass (copper-zinc alloy). As another example, copper alloys may include copper combined with other metallic elements, including nickel, aluminum, and / or lead. Copper-phosphorus alloys are also considered. The copper-containing particles 46 may be a mixture of two or more of metallic copper, copper alloys, and non-metallic copper-containing materials.
[0185] Copper-containing particles 46 are provided in paste 32 as a powder described by a particle size distribution. For example, the particle size distribution of a copper powder may include particles with sizes ranging from 10 μm to 22 μm. That is, the powder contains particles with an average particle size ranging from a maximum of 10 μm to 22 μm within the said range. Further, a narrower particle size distribution of the copper-containing particles 46 includes particles with sizes ranging from 10 μm to 20 μm. Other exemplary examples include a gradually narrowing particle size distribution: particles ranging from 7.5 μm to 14.7 μm (these are D... 10 and D 90 ), 1.8μm to 7.7μm (these are D 10 and D 90 ), 1.2μm to 3.2μm (these are D 10 and D 90 ), or 0.2μm to 1.6μm (these are D ... 10 and D 90 The particle size distribution is within the range of [specific particle size distribution]. The copper-containing particles 46 can be particles from a powder having a particle size distribution (e.g., one of the exemplary distributions above), or a mixture of multiple different powders such that multiple different particle size distributions are mixed in the paste 32. The particle size distribution is related to the surface area per unit weight of powder. Therefore, as the particle size distribution shifts towards smaller particles, the surface area per gram of powder increases.
[0186] For example, coarse copper-containing powder 46 can be mixed with fine copper-containing powder 46. The fine copper-containing powder 46 can fill the gaps between the larger copper-containing particles 46 in the paste 32. This results in a bimodal particle size distribution of the copper-containing particles 46 in the paste 32 and can maximize the volume of copper in the paste 32. In this way, any combination of two or more of the particle size distributions identified above can be mixed together to adjust the volume percentage of copper in the paste 32 to a desired range. For binary mixtures, the ratio of copper-containing powders of different sizes can range from 60 wt% coarse to 40 wt% fine to 90 wt% coarse to 10 wt% fine by weight. For example, coarse copper powder with a particle size distribution in the range of 10 μm to 20 μm can be mixed with fine copper powder with a particle size distribution in the range of 1.2 μm to 3.2 μm at a ratio of 90 wt% coarse to 10 wt% fine. Other ratios of two or more copper powders are possible. For example, coarse copper powder with a particle size distribution ranging from 7.5 μm to 14.7 μm can be mixed with fine copper powder with a particle size distribution ranging from 1.2 μm to 3.2 μm at a ratio of 70% coarse to 30% fine by weight. As an example of four different copper-containing powders, a particle size distribution ranging from 10 μm to 22 μm is mixed with three other copper-containing powders with particle size distributions ranging from 7.5 μm to 14.7 μm, 1.8 μm to 7.7 μm, and 1.2 μm to 3.2 μm, respectively, at weight ratios of 37:21:12:30. The copper-containing powders according to embodiments of the invention are commercially available from Bean Town (copper sheets), Chemical Store (commodity Cu112SP), ACuInternational (commodities 610 and 603), and Ames Goldsmith (commodity C1-2000).
[0187] It should be understood that Figure 4 The copper-containing paste 32 shown is a schematic diagram. Although the particles 42 within the paste 32 are shown to be spherical, embodiments of the invention are not limited to any single particle being spherical. Other particle shapes are possible, namely flake-like, needle-like, multifaceted, dendritic, sponge-like, circular, porous, elliptical, linear, and decorative, to name just a few.
[0188] Reference Figure 4The paste 32 contains other particles 42 that differ in composition from the copper-containing particles 46. In an exemplary embodiment, the other particles 42 in the paste 32 include nanoparticles 50. Each nanoparticle 50 is a discrete object, wherein all three dimensions are equal to or less than 100 nm. The nanoparticles 50 can form agglomerates or aggregates, in which case the agglomerates or aggregates can be measured up to 1 μm in each orthogonal direction. In one embodiment, the nanoparticles 50 are metals, metal oxides, and / or metal hydroxides of one or more of nickel (Ni), copper (Cu), lead (Pb), cobalt (Co), manganese (Mn), and silver (Ag). By way of example only, mixed elemental nanoparticles may include Cu, Ni, and Pb; Ni, Ni, and Pb; or Mn, Mn, and Pb. For example, nanoparticles 50 include nanoparticles of mixed oxides of Cu / Ni / Pb, Cu-Ag / Ni / Pb nanoparticles, mixed oxides of Co / Co / Pb nanoparticles, mixed oxides of Ni-Co / Ni / Pb nanoparticles, mixed oxides of Ni-Ag / Ni / Pb nanoparticles, and mixed oxides of Mn / Mn / Pb nanoparticles. As described below, each metal in the A / B / C symbols (e.g., Cu / Ni / Pb) can be provided by a metal salt to synthesize Ni / Ni / Pb nanoparticles, wherein Ni is provided by two different nickel-containing salts. Those metals can be oxidized during synthesis. Nanoparticles 50 may be doped with one or more of phosphorus (P), chloride (Cl), and boron (B), possibly due to the process of synthesizing nanoparticles 50. See below for reference. Figure 7A and Figure 7B An exemplary process for manufacturing nanoparticles 50 is described.
[0189] The amount of nanoparticles 50 contained in paste 32 is sufficient to reduce or eliminate oxidation of metallic copper or copper alloys in paste 32 or formed during the manufacture of solar cell 12, as further described below, while also reducing copper diffusion into wafer 14 during use of solar cell 12. Nanoparticles 50 also enable etching of antireflective coating 20 and allow electrical connection between copper and wafer 14. The reduction in copper diffusion can be achieved by forming a barrier layer between the copper of fingers 26 and wafer 14 during manufacturing. Without being bound by any theory, it is assumed that nanoparticles 50 participate in the formation of the barrier layer, such that the elements of nanoparticles 50 form an interface between the silicon of wafer 14 and the copper from copper-containing particles 46. For example, nanoparticles 50 may be present in paste 32 in an amount up to 17% by weight. Furthermore, as another example, nanoparticles 50 may be present in paste 32 at a maximum detectable amount of up to 5% by weight; a maximum detectable amount of up to 3% by weight; about 0.2% by weight (or close to the lower limit of detection) to a maximum of 3% by weight; or about 0.2% by weight to a maximum of 5% by weight. Mixtures of different nanoparticles are also considered, wherein the total weight of the mixture falls within the above ranges. For example, a mixture of nanoparticles 50 may be 50% by weight Ni / Ni / Pb nanoparticles and 50% by weight Cu / Ni / Pb nanoparticles.
[0190] like Figure 4 and Figure 5 As shown, the copper-containing particles 46 can be surface-modified. In one embodiment, the particles 46 are coated with smaller particles 56, which surround at least a portion of each individual copper-containing particle 46. The copper-containing particles 46 are substantially encapsulated by the smaller particles 56. The particles 56 can cover the entirety of each particle 46. However, the particles 56 can only cover small patches of each surface of the particles 46, so the particles 56 can be unevenly distributed on the surface of each particle 46. In this arrangement, the uncovered areas of the particles 46 are exposed within the paste 32. This configuration of smaller particles covering larger particles results in an increase in surface area measured from the surface area of the uncoated particles 46 to the surface area of the copper particles 46 coated with particles 56. The surface area can increase by up to 20%. For example, the surface area is 0.6 m². 2 / g of uncoated copper particles can be modified to have a surface area of at least 0.83m². 2 / g. As another example, copper-containing particles 46 can be modified to have a surface area of 0.83m². 2 / g to 1.61m 2 Within the range of / g. In one embodiment, the surface area increase is 1.5%. Therefore, as an example, the range of surface area increase is 1.5% to 20%. However, surface modification can also produce a surface area increase of up to 3,000% compared to the surface area of uncoated particles 46. Surface area can be measured using the BET method. The Gemini VII Series 2390 surface area analyzer is used to measure surface area. It contains copper particles 46 and nanoparticles 50. In the FlowPrep060 system, degassing was performed at 160°C for 2 hours under an inert gas (nitrogen, N2) flow. The degassing process desorbs contaminants such as water from the powder surface, and the gas removes them from the sample tube. The Gemini unit used N2 physisorption to measure the adsorption isotherm of the powder. Multi-point measurements of the isotherm were used to calculate the powder's surface area using the Brunauer-Emmett-Teller equation. Controlling the surface area of the copper-containing particles 46 controls the formation of the interface between the fingers 26 and the wafer 14.
[0191] according to Figure 9A In the process shown, copper-containing particles 46 can be coated with particles 56. Particles 56 can be metallic or oxides / hydroxides of various metals. For example, particles 56 can be oxides / hydroxides of metallic copper and / or at least one of copper (Cu), nickel (Ni), and manganese (Mn). Particles 56 may be doped with phosphorus (P) due to the process of their synthesis, as described below. Particles 56 can nucleate and grow on the surface of the copper-containing particles 46. Thus, particles 56 can be at least weakly bonded to the surface of each copper-containing particle 46. Embodiments of the invention are not limited to the bonding between particles 56 and any other particles in the paste 32. Particles 56 located at the surface are positioned to protect the copper-containing particles 46 from oxidation or other undesirable reactions during manufacturing. The composition of particles 56 can form at least a portion of the interface between the fingers 26 and the wafer 14.
[0192] Continue to refer to Figure 4The paste 32 contains second oxide particles 52. Similar to particles 56, the second oxide particles 52 can also participate in reducing or inhibiting the oxidation of copper in the copper-containing particles 46, while enabling the etching of the anti-reflective coating 20. Therefore, the second oxide particles 52 enable electrical connections between the copper of the fingers 26 and the wafer 14 during manufacturing, as described below. In addition, or alternatively, the second oxide particles 52 can help form an interface between the copper in the fingers 26 and the silicon in the wafer 14 to prevent the diffusion of copper into the silicon during use of the solar cell 12. The second oxide particles 52 can be reduced to their constituent metals during heating, and then it can be possible to reduce at least the oxide / hydroxide nanoparticles 50 and / or the oxide / hydroxide of particles 56. Furthermore, the second oxide particles 52, alone or in combination with one or both of nanoparticles 50 and particles 56, can form a liquid sintering aid during the manufacture of the solar cell 12. Liquid phase sintering is a technique used for sintering alloys and composite materials. In composite materials containing two materials, the second material will have a lower melting point than the first material. Therefore, one material will melt at a given processing temperature, while the other remains solid. When the main material is soluble in the liquid phase, the liquid wets the particles and generates capillary forces that hold the particles together in a tightly packed structure. Furthermore, the liquid enables a higher diffusion rate, which facilitates faster sintering and lower processing temperatures. The ratio of nanoparticles 50 to second oxide particles 52 and particles 56 in the paste 32 can at least partially control the etching process between the paste 32 and the anti-reflective coating 20 during sintering.
[0193] Regarding the oxides in the reduction paste 32, the second oxide particles 52 can be one or more metal oxides having a more negative Gibbs free energy of formation than at least one of the oxides of nanoparticles 50 and particles 56. For example, the second oxide particles 52 may have a greater negative Gibbs free energy of formation than at least one of copper oxides (Cu2O, CuO), lead oxides (PbO, PbO2), or nickel oxides (NiO) at the temperature during manufacturing when wafer 14 and paste 32 are heated. In one embodiment, the second oxide particles 52 are antimony oxide (Sb2O3) particles. Other second oxide particles 52 include, but are not limited to, tin oxides (SnO, SnO2), tellurium oxide (TeO), manganese oxides (MnO, MnO2), and phosphorus oxides (P4O3). 10The oxides used are bismuth oxide (Bi₂O₃), chromium oxide (Cr₂O₃), and aluminum oxide (Al₂O₃). Other oxides in the paste 32 can be reduced using these oxides, depending on the oxidation state of the second oxide particles 52, the melting point temperature of the second oxide particles 52, the processing temperature and partial pressure of the reducing environment surrounding the second oxide particles 52. Furthermore, the second oxide particles 52 may include glass frit particles, such as lead-containing silicate glass or other metallic glasses containing one or more oxide components having a more negative Gibbs free energy of formation than at least one of Cu₂O, CuO, PbO₂, PbO, and NiO. Exemplary glass frit particles include borate glasses, such as B₂O₃-PbO-ZnO glass, and silicate glasses, such as PbO-SiO₂-B₂O₃-Al₂O₃ glass.
[0194] The paste 32 may include 1% to 15% by weight of second oxide particles 52. The surface area of the second oxide particles 52 may be 2m². 2 / g to 2.5m 2 The ratio of the second oxide particles 52 to the nanoparticles 50 can determine the amount of oxide reduced during heating and / or the amount of sintering aid formed. In one embodiment, the ratio of the second oxide particles 52 to the nanoparticles 50 is in the range of 0.50 to 16.96 by weight. In another embodiment, the ratio of the second oxide particles 52 to the metal-oxide-containing nanoparticles is in the range of 1.50 to 3.51 by weight. As used herein, “consistently of” means that no other elements or particles are intentionally added to the paste. However, the content of other elements in oxide or metal form from the powder or manufacturing process is taken into consideration.
[0195] Reference Figure 4 and Figure 5 Once the paste 32 is dispensed, the substrate 40 and the paste 32 are exposed to temperatures from 20°C to 400°C, or more specifically from 20°C to 200°C, for drying. During drying, at least some of the organic carrier 44 is removed from the paste 32. Figure 5 The middle part is schematically shown by arrow 54.
[0196] After drying, the particles 42 of the paste 32 are fired during the metallization process to produce fingers 26 and / or a back conductor 30. In one embodiment, the fabrication of the solar cell 12 (including drying and firing) is completed in air. That is, the atmosphere during drying and firing is not controlled or altered by adding inert or reducing gases. During firing, the particles 42 are exposed to air at a temperature of 600°C to 930°C for 0.8 to 10 seconds, depending on the furnace temperature distribution, belt speed, and composition of the paste 32. At these temperatures and times, in one embodiment, at least one organic binder remaining in the organic carrier 44 decomposes and forms a reducing environment surrounding the particles 42. This environment is believed to reduce the second oxide particles 52. The reduction of at least some of the second oxide particles 52 produces at least one metal from the second oxide particles 52. For example, the composition of the organic carrier 44 is believed to reduce antimony oxide (Sb₂O₃) to metallic antimony (Sb). As another example, the organic carrier 44 may also reduce lead oxide to lead (Pb).
[0197] Conversely, the metal from the second oxide particles 52 reduces at least some of the nanoparticles 50 and / or particles 56 on the copper-containing particles 46. Continuing with Sb as an example, the generated metal Sb reduces the oxides of the nanoparticles 50 and particles 56. In the presence of PbO, metal Sb can be reduced to Pb by PbO, and Pb can contribute to the reduction of copper oxides. Therefore, by virtue of the characteristics of particles 42 in paste 32, a cascade reduction reaction can be facilitated by the decomposition of the organic carrier 44. In this cascade reduction, one oxide is reduced to a metal. This metal then reduces another oxide in the mixture of particles 42. Depending on the temperature; the composition and volume of the nanoparticles 50, the second oxide particles 52, and particles 56; and the proportion of the organic carrier 44 in paste 32, the cascade reduction reaction can reduce all oxides in paste 32 to their constituent metals. This can include any copper oxides present in paste 32. In this case, the paste containing most of the metal oxides comprises a complex of different metals.
[0198] At the temperatures exposed to during sintering, the reduced nanoparticles 50 and second oxide particles 52 can form a liquid sintering aid and can reduce and / or coat the copper-containing particles 46. The metal from the nanoparticles 50 and second oxide particles 52 can react with the anti-reflective coating 20. This particle combination is thought to produce an etchant.
[0199] like Figure 5 and Figure 6 As shown, during firing, particles 42 are sintered to form fingers 26 with a width W1 and a height H1. Typically, these dimensions are smaller than the paste 32 after dispensing (see [reference]). Figure 4The corresponding width W2 and height H2, for example Figure 4 As shown. After firing / sintering, the width W2 of the paste 32 is reduced to the width W1 of the fingers 26. Furthermore, the height H2 of the paste 32 decreases from the firing / sintering stage to H1. This reduction in height is at least partly due to the reaction / etching of the antireflective coating 20, as further described below. Dimensions such as H1 and W1 are controlled by factors including, for example, if screen printing, (i) printing press settings (e.g., squeegee pressure and speed), (ii) paste rheology and composition, (iii) screen parameters (e.g., aperture size), and (iv) firing conditions.
[0200] Although paste 32 initially includes oxide particles 50 and 52, fingers 26 are metallic because some or all of the oxide particles are reduced during the sintering of paste 32. Except for the external surfaces of fingers 26 exposed to air, which may form native oxides (e.g., CuO and / or Cu2O, Sb2O3, etc.) upon exposure to air, fingers 26 may be free of internal oxides. During sintering, particles and reaction products, particularly the metals from nanoparticles 50 and the second oxide particles 52, penetrate the antireflective coating 20 along with copper-containing particles 46. During sintering, the metals, nanoparticles 50 and / or the second oxide particles 52 and / or the metals of those oxide particles contact the antireflective coating 20 and can generate reaction products between the metal and the material of coating 20. For example, when the antireflective coating 20 is SiN, the reaction products may include metal silicides and / or metal nitrides. These reaction products can form an interface 58 (generally in…) between the copper or copper-containing grains of fingers 26 and the wafer 14. Figure 6 (As indicated in the diagram) and may contain silicides. After penetrating the antireflective coating 20, the metal and copper-containing particle 46 composite that ultimately forms the fingers 26 is electrically connected to the n-type region 16 of the wafer 14. Interface 58 can prevent copper from diffusing into the silicon of the wafer 14 during the manufacture and use of the solar cell 12. Interface 58 can form the boundary between the copper or copper-containing grains and the silicon of the wafer. The composition of the grain boundary at interface 58 may include lead, nickel, copper, cobalt, manganese, antimony, tellurium, and bismuth and / or another metal found in the nanoparticles 50 or the second oxide particles 52. In one embodiment, the back conductor 30 (e.g., aluminum) is co-fired with the paste 32 in air. Therefore, the fingers 26 and the back conductor 30 can be fired simultaneously or separately. It should be noted that as the target width W1 of the fingers 26 decreases, the surface area of the copper-containing particles can be reduced.
[0201] For reference Figure 4The paste 32 comprises a plurality of particles 42. Each of these particles can be synthesized prior to its introduction into the organic carrier 44. As an example, nanoparticles 50 can be synthesized from various metal salts. Figure 7A and Figure 7B An exemplary flowchart for synthesizing nanoparticles 50 that can be contained in paste 32 is shown.
[0202] exist Figure 7A In the exemplary process shown, Cu / Ni / Pb nanoparticles 50 were synthesized. As illustrated, in reactor 60, a first aqueous stream 62 of copper nitrate and ammonium hydroxide was added and stirred. The ammonium hydroxide precipitated the copper hydroxide and the metal ammonia complex. A second stream 64 of an aqueous dispersion of sodium borohydride was added to reactor 60 at a predetermined rate and the solution was stirred. This reaction produced copper oxide / hydroxide nanoparticles 50.
[0203] If an additional coating is desired on the copper oxide / hydroxide core, an additional stream is added to reactor 60 containing the copper oxide / hydroxide nanoparticles. For example, if a nickel oxide coating is desired on the copper oxide / hydroxide nanoparticles, a third stream 66 of aqueous nickel chloride and aqueous sodium borohydride is added to reactor 60 and stirred. This coats the copper oxide / hydroxide nanoparticles with a nickel oxide layer. By adding a fourth stream 68 of aqueous lead nitrate to reactor 60, a third layer of lead oxide / hydroxide is coated onto the nickel oxide layer. This creates a lead oxide / hydroxide coating on the nickel oxide.
[0204] The following is Figure 7A The possible reactions and side reactions that occur during the synthesis are shown.
[0205] Equation 1.
[0206] Primary stoichiometric reactions that occur in the reactor.
[0207] 2Cu(NO3)2(aq) + 4NaBH4(aq) →
[0208] 2Cu(s)+4Na(NO3)(aq)+2B(OH)3(aq)+H2(g)+B2H6(g)
[0209] Equation 2.
[0210] Assume that excess NaBH4 reacts with H2O. In one process, a substoichiometric amount is used.
[0211] NaBH4(aq)+4H2O→NaB(OH)4(aq)+4H2(g)
[0212] Equation 3.
[0213] Assume that B2H6 reacts completely with H2O, and that all Cu is reduced to Cu2O upon the addition of NiCl2.
[0214] B2H6(g)+6H2O(1)→2B(OH)3(aq)+6H2(g)
[0215] Equation 4.
[0216] Equation 4a.
[0217] Cu has multivalent properties, therefore it can react with Cu 2+ Ionic reactions.
[0218] Cu(s) + Cu 2+ (aq)→2Cu + (aq)
[0219] Equation 4b.
[0220] Cu + Can be with Cl - Ionic reactions.
[0221] Cu + (aq)+Cl - (aq)→CuCl(s)
[0222] Equation 4c.
[0223] CuCl can form Cu2O.
[0224] 2CuCl(s)+H2O(1)→2HCl(aq)+Cu2O(s)
[0225] Equation 5.
[0226] NiCl2 reacts with NaBH4 to coat Cu2O particles with Ni.
[0227] 2NiCl2(aq)+4NaBH4(aq)→2Ni(s)+4NaCl(aq)+2B(OH)3(aq)+H2(g)+B2H6(g)
[0228] Equation 6.
[0229] A substitution reaction occurs when Pb(NO3)3 is added.
[0230] 3Ni(s)+2Pb(NO3)3(aq)→3Ni(NO3)2(aq)+2Pb(S)
[0231] Both Ni and Pb shells can be oxidized to NiO and PbO, respectively. Less than stoichiometric amounts can be used in the reaction. If so, assuming NaBH4 is the limiting factor, Equation 1 becomes Equation 7, and Equation 5 becomes Equation 8.
[0232] Equation 7.
[0233] Non-stoichiometric reactions that occur in batch reactors.
[0234] 0.37Cu(NO3)2(aq)+0.74NaBH4(aq)→0.37Cu(s)+0.74Na(NO3)(aq)+0.37B(OH)3(aq)+0.185H2(g)+0.185B2H6(g)
[0235] The mass balance also assumes that there is no excess NaBH4 reacting with H2O. It is assumed that the reaction in Equation 2 did not occur.
[0236] Equation 8.
[0237] The reaction of NiCl2 with NaBH4 is a non-stoichiometric reaction of Ni-coated Cu2O particles.
[0238] 0.1NiCl2(aq) + 0.2NaBH4(aq) →
[0239] 0.1Ni(s)+0.2NaCl(aq)+0.1B(OH)3(aq)+0.05H2(g)+0.05B2H6(g)
[0240] Equation 9.
[0241] A substitution reaction occurs when Pb(NO3)2 is added.
[0242] 0.1Ni(s)+0.2Pb(NO3)3(aq)→0.1Ni(NO3)2(aq)+0.07Pb(s)+0.13Pb(NO3)3(aq)
[0243] For non-stoichiometric quantities, Equation 3 becomes Equation 10.
[0244] Equation 10.
[0245] The reaction of B2H6 with H2O.
[0246] 0.235B2H6(g)+1.41H2O(1)→0.47B(OH)3(aq)+1.41H2(g)
[0247] After addition and reaction, nanoparticles 50 are separated from the supernatant by centrifugation at 70°C. The solid residue (which consists of Cu / Ni / Pb nanoparticles) is then dried at 72°C. The nanoparticles 50 can be crushed to separate the agglomerates, then sieved and prepared for use in paste 32.
[0248] Figure 8 Depicting according to Figure 7A Transmission electron microscopy images of three different Cu / Ni / Pb nanoparticles produced by the process shown. As illustrated, energy-dispersive X-ray diffraction (EDXRD) patterns for Cu are shown in (b), (h), and (n); for oxygen in (e), (i), and (p); for Ni in (d), (j), and (p); for Cl in (e), (k), and (q); and for Pb in (f), (l), and (r). The elemental diagrams generally indicate the presence and uniform distribution of Cu, O, and Ni in nanoparticles 50. Pb and Cl appear to have a more irregular distribution.
[0249] Figure 7B A similar process is shown in the figure. However, the resulting nanoparticles 50 are Ni / Ni / Pb nanoparticles. That is, the core of the nanoparticles is nickel oxide, with a nickel oxide coating, and then a lead oxide coating. Growing the nickel oxide in two stages produces larger particle sizes. In this respect, a first stream 74 of nickel nitrate and ammonium hydroxide is added to reactor 60. Subsequently, in a manner similar to that in the reference… Figure 7A The reactor 60 is then fed a second stream 64, followed by a third stream 66 and a fourth stream 68. After centrifugation 70 and drying 72, the Ni / Ni / Pb nanoparticles 50 are ready to be added to the paste 32.
[0250] Reference Figure 9A In one embodiment, the copper-containing particles 46 are surface-modified with a metal oxide before mixing the paste 32. Figure 9A In the flowchart, copper-containing particles 46 are placed in reactor 76. The copper-containing particles 46 may be pretreated with oleic acid, or the particles 46 may be untreated before being placed in reactor 76. A metal salt (e.g., nickel nitrate) is dissolved in an aqueous ethylene glycol solution containing polyvinylpyrrolidone. The solution of the dissolved metal salt and ethylene glycol is injected into reactor 76 as a first stream 80 and mixed with an aqueous dispersion of a reducing agent, such as sodium hypophosphite (NaPO2H2), as a second stream 82. The solution is continuously stirred and heated in reactor 76 for a specified time. The metal ions are reduced at high temperature, and the resulting reaction produces a solution coated with copper-containing powder of a metal or metal oxide / hydroxide. As an example, in Figure 9AIn the reactor 76, copper-containing particles 46 are coated with nickel oxide and / or nickel hydroxide. Particles 56 may be coated or decorated with particles 46. It should be noted that the nickel oxide / hydroxide may contain phosphorus and may depend on the concentration of the reducing agent added to the reactor 76. The coated particles 46 are separated from the solution at 84 (e.g., by centrifugation) and then dried at 86.
[0251] Although reference Figure 9A Nickel salts have been described, but various other metal salts can be used to treat copper-containing particles 46. As an example, the coating on the copper-containing particles 46 can contain cobalt (Co) and / or manganese (Mn), etc. By adding the copper-containing particles 46 to reactor 76, the surface of the copper-containing particles 46 can be coated by particles 56. The amount of coating 56 can be controlled by maintaining the mixture above a specific temperature for a certain period of time. Typically, the surface area of the particle-coated copper-containing particles 46 increases with increasing time and temperature. For example, the total surface area of the copper-containing particles 46 with a particle-coated surface increases. Typically, the surface area of the particle-coated copper-containing particles 46 is increased by at least 10% and can be as high as 3,000% compared to the uncovered particles 46.
[0252] Then each of the particles 42 is mixed with the organic carrier 44. (See reference...) Figure 9B Organic carrier 44, nanoparticles 50, second oxide particles 52, and copper-containing particles 46 are mixed to form a screen-printable paste 32. For example... Figure 9B As shown, the organic carrier 44 comprises polyvinylpyrrolidone, dissolved in a solvent (e.g., polyethylene glycol) and added at 90 to the vacuum mixer 92. Nanoparticles, for example, from... Figure 9A Cu / Ni / Pb nanoparticles 50 are also placed in vacuum mixer 92 at position 94. Nanoparticles 50 and organic support 44 are mixed under vacuum for a specified time. At position 96, second oxide particles 52 are placed in vacuum mixer 92. The mixture is then mixed under vacuum. At position 98, copper-containing particles 46 are placed in vacuum mixer 92 and mixed under vacuum. If present, at position 100, additional copper-containing particles 46 are placed in vacuum mixer 92 and mixed under vacuum. Figure 9B In the illustrated embodiment, particles 42 in streams 94, 96, 98, and 100 are added to the vacuum mixer 92 in a predetermined order based on their surface area. In the exemplary embodiment, particles 42 with the largest surface area are added first.
[0253] Once all carriers 44 and particles 42 have been added to the vacuum mixer 92, the mixture is mixed under vacuum for a specified time. The mixture is then milled at 102. This may include using a three-roll mill, ball mill, or other particle dispersion equipment. The milling process helps to separate particle agglomerates and promotes homogenization and degassing of the mixture. After milling, the mixture is aged at 104 at a high temperature (e.g., 100°C) for a specified length of time to improve the wetting of the organic carriers 44 on the particles 42. The mixture may then undergo another milling at 106, and additional organic carriers 44 (not shown) may be added to reach a predetermined viscosity before the paste 32 is ready for use.
[0254] To facilitate a more complete understanding of the present invention, the following non-limiting embodiments are provided.
[0255] Example
[0256] In the following embodiments, the powder may be doped with phosphorus (P) or another element. This is indicated by the symbol Cu / element symbol "(?)P", for example, "Cu / Ni(?)P", which indicates that copper-containing particles having nickel on their surface may be doped with phosphorus. It is considered that copper or nickel materials (in the form of metal, oxide, or hydroxide) are doped with P. Embodiments of the invention are not limited to those doped with P or any other element.
[0257] Example 1. Synthesis of copper-containing particles with nickel
[0258] The synthesis of copper particles with a nickel-containing microparticle-coated surface is illustrated by the following example. 4.50 g of polyvinylpyrrolidone (PVP) MW 40,000 was dissolved in 300 mL of ethylene glycol in a 2000 mL flask. The mixture was stirred using a paddle mixer. This mixture was prepared one day prior to use. 144.78 g (0.5 mol) of nickel nitrate hexahydrate was added to the PVP / ethylene glycol mixture and mixed until dissolved. 381.24 g (6.0 mol) of copper powder (Example 1 was performed using each of the following copper powders: 1.) 10 μm to 22 μm, 2.) 7.5 μm to 14.7 μm, 3.) 1.8 μm to 7.7 μm, 4.) 1.2 μm to 3.2 μm) was gradually added to the mixture. The mixture was continuously mixed between additions to prevent agglomeration. The mixture was stirred using a paddle mixer for 30 minutes. Add 216.24 g (2.0 mol) sodium hypophosphite monohydrate and 150 mL distilled water to the mixture. Stir the mixture with a paddle mixer for 30 minutes.
[0259] Place an aluminum foil cap with holes for a paddle mixer around the top of the beaker. Place the beaker on a hot plate, raise the plate temperature to 350°C, and heat the mixture for 40 minutes with continuous stirring using a paddle mixer. Allow the mixture to reach 90°C. After 40 minutes, turn off the hot plate.
[0260] Allow the mixture to cool and transfer it to a centrifuge container. Centrifuge the material at 3000 rpm for 3 minutes. Discard the supernatant into a waste bottle. Add more mixture to the centrifuge container (or add distilled water if the mixture beaker is empty). Stir and shake the flask thoroughly. Repeat centrifugation and decantation until the supernatant is clear and colorless. Place the solid particles on a drying tray and allow them to dry overnight.
[0261] The dried copper-containing particles coated with nickel oxide / hydroxide are crushed using a grinder and then sieved through a 325-mesh sieve.
[0262] The following equation is assumed to represent the reaction that occurs during the synthesis. Nickel oxide will be deposited on the surface of copper.
[0263] Equation 1. The main stoichiometric reaction occurring in a batch reactor. Nickel nitrate is the rate-limiting reagent.
[0264] Ni(NO3)2(aq)+2NaH2PO2(aq)+2H2O→Ni(s)+2Na(HPO3)(aq)+3H2(g)
[0265] Example 2. Synthesis of copper-containing particles with cobalt
[0266] The synthesis of copper particles with a cobalt-containing microparticle-coated surface is illustrated by the following examples. The metal used in the coating can be changed by replacing the metal salt in Example 1 with cobalt nitrate hexahydrate. 4.50 g of polyvinylpyrrolidone (PVP) 40,000 was dissolved in 300 mL of ethylene glycol in a 2000 mL flask. The mixture was stirred with a paddle mixer. This mixture was prepared one day prior to use. 145.52 g (0.5 mol) of cobalt nitrate hexahydrate was added to the PVP / ethylene glycol mixture and mixed until dissolved. 381.24 g (6.0 mol) of copper powder (using copper powder with size distributions of 10 μm to 22 μm and 1.2 μm to 3.2 μm respectively in Example 2) was gradually added to the mixture. The mixture was continuously mixed between additions to prevent agglomeration. The mixture was stirred with a paddle mixer for 30 minutes. 216.24 g (2.0 mol) of sodium hypophosphite monohydrate and 150 mL of distilled water were added to the mixture. Stir the mixture using a paddle mixer for 30 minutes.
[0267] Place an aluminum foil lid with holes for a paddle mixer around the top of the beaker. Place the beaker on a hot plate, raise the plate temperature to 350°C, and heat the mixture for 40 minutes with continuous stirring using a paddle mixer. Set the hot plate to 350°C and allow the mixture to reach the desired temperature of 90°C. After 40 minutes, turn off the hot plate. Allow the mixture to cool.
[0268] Transfer the mixture to a centrifuge container and centrifuge at 3000 rpm for 3 minutes. Discard the supernatant into a waste bottle. Repeat centrifugation and decantation until the supernatant is clear and colorless. Empty the solid particles into a drying tray and dry overnight. Crush the dried, particle-coated copper powder using a grinder and sieve through a 325-mesh sieve.
[0269] Example 3. Synthesis of copper-containing particles with manganese
[0270] The synthesis of copper particles with a manganese-containing microparticle-coated surface is illustrated by the following examples. The metal used in the coating can be changed by replacing the metal salt in Example 1 with manganese nitrate tetrahydrate. 4.50 g of polyvinylpyrrolidone (PVP) 40,000 was dissolved in 300 mL of ethylene glycol in a 2000 mL flask. The mixture was stirred with a paddle mixer. This mixture was prepared one day prior to use. 125.51 g (0.5 mol) of manganese nitrate tetrahydrate was added to the PVP / ethylene glycol mixture and mixed until dissolved. 381.24 g (6.0 mol) of copper powder (Example 3 was carried out using 10 μm to 22 μm copper powder and 1.2 μm to 3.2 μm copper powder, respectively) was gradually added to the mixture. The mixture was continuously mixed between additions to prevent agglomeration. The mixture was stirred with a paddle mixer for 30 minutes. 216.24 g (2.0 mol) of sodium hypophosphite monohydrate and 150 mL of distilled water were added to the mixture. Stir the mixture using a paddle mixer for 30 minutes.
[0271] Place an aluminum foil cap with holes for a paddle mixer around the top of the beaker. Place the beaker on a hot plate, raise the plate temperature to 350°C, and heat the mixture for 40 minutes with continuous stirring using a paddle mixer. In one embodiment, the hot plate is set to 350°C, allowing the mixture to reach 90°C. After 40 minutes, turn off the hot plate and allow the mixture to cool.
[0272] Transfer the mixture to a centrifuge container and centrifuge at 3000 rpm for 3 minutes. Discard the supernatant into a waste bottle. Repeat decantation and centrifugation until the supernatant is clear and colorless. Empty the solid particles into a dry dish and dry overnight.
[0273] The dried powder is crushed using a grinder and then sieved through a 325-mesh sieve.
[0274] Example 4. Surface area modification of copper-containing particles with nickel
[0275] The surface area of the coated copper powder can be controlled by varying the reaction time during synthesis. The surface area of the coated powder is directly related to the time the reaction mixture is held above the reaction temperature. When the reactants are held above this temperature, the amount of deposited material increases, which increases the surface area of the copper powder. Figure 10 Table 1 illustrates the effect of reaction temperature and time on the surface area of 1.2 μm to 3.2 μm copper powder subjected to coating consistent with Example 1.
[0276] Table 1
[0277]
[0278] Peak temperatures in the reactor and the time the reaction mixture was held above 85°C increased the surface area of the coated copper powder. In this example, the increase was 38% at 90°C and up to 5 times at 104°C.
[0279] The surface area of the coated powder is also related to the highest temperature experienced by the reactants during the reaction. Reactions using fine (1.2 to 3.2 micrometers) copper powder with an oleic acid coating are susceptible to temperature overshoot, where the oleic acid-coated copper powder foams during the reaction. The peak temperature is controlled by the time the hot plate is turned off.
[0280] Gaseous byproducts are trapped within the foam layer. At peak temperatures below 90°C, the foam layer collapses during cooling. In addition to the powder having a low surface area, the material also exhibits signs of oxidation (see Table 1). For reactions with higher peak temperatures, the foam layer remains above the reaction mixture until the material is ready for centrifugation.
[0281] When the reaction temperature exceeds 100°C, the foam layer collapses once the peak temperature is reached, reducing its thickness. This reduction in thickness, in addition to a slightly faster stirring rate, results in a faster cooling rate for the reaction. When the heating and cooling profiles of the laboratory-scale reaction are within a few degrees (i.e., directly superimposed), the measured surface area of the coated copper (comparing the two batches) is 0.002 m². 2 Within / g. However, even under matched heating and cooling conditions, the delay (approximately 1.5 hours) before centrifugation of the material resulted in a longer period of gas retention trapped in the foam. Consequently, the surface area of the coated material was found to increase by 0.126 m². 2 / g.
[0282] 11A to 11DThe properties of a paste containing unmodified copper powder with Ni / Ni / Pb nanoparticles and Sb₂O₃ particles are shown. These figures illustrate the effect of accelerated aging at 200 °C on (a) the short-circuit current density J. sc ( Figure 11A (b) Open circuit voltage V oc ( Figure 11B (b) Fill factor FF Figure 11C (d) Efficiency η( Figure 11D The average effect of ) is shown. Paste 1 was formulated with Sb₂O₃ and 100% Ni / Ni / Pb nanoparticles. See Table 12 (below). Copper powder was not coated. The results were normalized to their initial values at 0.01 hours. The error bars are the standard deviations of the results from 5 cells.
[0283] Examples 5 to 9. Durability testing methods for apparatuses metallized with copper-containing paste
[0284] The durability of fired solar cells is assessed by monitoring the open-circuit voltage (V) of the device. oc To determine. A constant V oc This indicates that copper has not penetrated into the silicon. To expedite testing, the cells are exposed to high temperatures. One testing method follows a peer-reviewed academic article on electroplated copper contacts on silicon solar cells. This test applies thermal stress to the cells at temperatures ranging from 150°C to 300°C to assess their reliability over a much shorter timeframe. These temperatures are above the solar cells' maximum operating temperature range of 80°C to 90°C. One drawback of this testing method is that the test temperatures are high enough that chemical interactions may occur between the materials, which would never occur during normal operation of the solar cell. Copper diffusion into the junction would lead to V... oc decline.
[0285] Example 5. Effect of nanoparticle composition on durability
[0286] Three copper-containing pastes were compared. Paste 2, paste 3, and paste 4 were formulated as shown in Table 2 (below). The nanoparticle components of the pastes consisted of the following: (i) 100% Cu / Ni / Pb nanoparticles, (ii) 50% Cu / Ni / Pb nanoparticles and 50% Ni / Ni / Pb nanoparticles, and (iii) 100% Ni / Ni / Pb nanoparticles. Figure 12A This study demonstrates that for batteries made from each of pastes 2, 3, and 4, after applying thermal stress to the battery at 200°C for up to 110 hours, the nanoparticle composition affects PV performance (i.e., open-circuit voltage, V0). oc The impact of ). Figure 12AThe error bars represent the standard deviation between 4 and 6 cells measured for each paste. The results were normalized to their initial values at 0.01 hours.
[0287] Figure 12B , Figure 12C , Figure 12D and Figure 12E This explains the impact of accelerated aging on PV performance, among which... Figure 12B and Figure 12D It consists of 100% Cu / Ni / Pb nanoparticles. Figure 12C It consists of 50% Cu / Ni / Pb nanoparticles and 50% Ni / Ni / Pb nanoparticles. Figure 12E It consists of 100% Ni / Ni / Pb nanoparticles.
[0288] Figure 12F , Figure 12G , Figure 12H and Figure 12I This demonstrates the effect of accelerated aging at 200℃ on (a) short-circuit current density J. sc ( Figure 12F (b) Open circuit voltage V oc ( Figure 12G (c) Fill factor FF ( Figure 12H ), and (d) efficiency η( Figure 12I The average effect of ) was considered. The results were normalized to their initial values at 0.01 hours. The error bars are the standard deviations of 4 to 6 cells measured for each paste.
[0289] Table 2
[0290]
[0291] Example 6. Effect of surface modification of copper-containing powder on durability
[0292] This example illustrates the effect of a copper-powder-containing microparticle coating on the PV performance of crystalline silicon solar cells from three different manufacturers. The copper powder used was the same coating as in Example 1. The prepared cells were subjected to thermal stress at 200°C for up to 110 hours. The performance of paste 5 in Table 3 is shown below. Figures 13A to 13H .
[0293] Table 3
[0294]
[0295] Example 7. Effect of the relative ratio of secondary oxide particles and nanoparticles in the paste on durability.
[0296] This example illustrates the effect of changing the proportion of second oxide particles in the paste by altering the ratio of Ni / Ni / Pb nanoparticles relative to the second oxide particles. The weight ratio of the two particle types is kept constant at 2.50. Figure 14A , Figure 14B and Figure 14C The PV performance of a monocrystalline silicon solar cell is shown, wherein the fingers are printed with the following pastes as shown in Table 4 (below): (a) paste 6, (b) paste 7, and (c) paste 8.
[0297] Thermal stress was applied to the battery at 150°C for up to 300 hours. The increased proportion of nanoparticles and second oxide particles in these pastes resulted in a copper volume (solids only) ranging from 85.50 vol% to 79.51 vol% Cu. With the increased proportion of nanoparticles and second oxide particles in the paste, the thickness of the glassy interface between the fingers and the wafer increased. The PV performance of the battery was maintained during accelerated aging tests by keeping the solids-only portion of the paste greater than 80 vol%.
[0298] Table 4
[0299]
[0300] The effect of accelerated aging tests at 150°C on the IV performance of monocrystalline silicon cells with a passivated emitter and rear cell (PERC) localized aluminum back surface field (Al BSF) metallized with paste is shown in the figure. Figure 14A , Figure 14B and Figure 14C middle.
[0301] Example 8. Effect of the relative proportion of the second oxide in the paste on durability.
[0302] This embodiment illustrates the effect of the proportion of second oxide particles in the paste on battery performance during accelerated aging tests at 150°C for up to 200 hours. The weight ratio of second oxide particles to nanoparticles in the paste was varied by changing the proportion of second oxide particles in the paste used for printing the fingers. The total surface area contribution of the coated copper-containing powder used in the paste was fixed at 0.74 m² / gram of paste. 2 Coating. Table 5 shows the composition of the paste used for printing the fingers. All batteries use the same bus paste formulation.
[0303] Table 5
[0304]
[0305] Figure 15A , Figure 15B , Figure 15C , Figure 15D , Figure 15E and Figure 15F The effect of accelerated aging tests at 150°C on the PV performance of monocrystalline Si cells with PERC localized Al BSF cells metallized using the pastes listed in Table 5 is shown. All pastes exhibited stable Vp throughout the testing period. oc The resistance of the finger structure and, consequently, the fill factor (FF) were found to be influenced by the ratio of the second oxide to nanoparticles in the paste. Optimal durability was found using a ratio of 1.50. Data at second oxide / NP = 0.5 were likely discarded due to the small sample size and slightly off-target firing conditions.
[0306] Example 9. Effect of surface area of copper-containing particles with nickel on durability
[0307] The amount of nickel coating on copper-containing powder was quantified by measuring the surface area of the material. The amount of coating in the paste was varied by changing the surface area of the fine copper powder in the paste. The amount of coating on the copper powder was 0.74m (paste 11). 2 / gram of paste, (paste 14) 0.83m 2 / gram of paste, (paste 15) 1.01m 2 / gram of paste, and (paste 16) 1.10m 2 / gram of paste. All pastes used a 1.50 ratio of secondary oxide particles to nanoparticles. Table 6 shows the composition of the paste used for printing fingers. All batteries used the same bus paste formulation.
[0308] Table 6
[0309]
[0310] Figure 16A , Figure 16B , Figure 16C , Figure 16D and Figure 16E The normalized PV performance of monocrystalline Si cells with PERC localized Al BSF metallized using the pastes in Table 6 is shown in the accelerated aging test at 200°C. sc Normalized V oc The effects of normalized FF, normalized η, and normalized resistance across the entire finger. When the surface area of the copper-containing particles with nickel is greater than 1.0 m². 2 When the paste content is reduced by 1.01m, the resistance of the fingers increases significantly; therefore, this leads to a decrease in the flyback effect (FF). Using 1.01m... 2 / gram of paste surface area, producing the lowest FF reduction during the test ( Figure 16C ).
[0311] Figure 17A , Figure 17B , Figure 17C and Figure 17D The effect at 200°C was shown. Figure 16A , Figure 16B , Figure 16C , Figure 16D and Figure 16E Examples of accelerated aging of the IV performance of the pastes shown are illustrated. When the surface area of the copper particles in the paste is low (paste 11), the diffusion barrier layer formed by the paste appears insufficient, and a significant increase in the dark IV curve is observed; resulting in lower FF and performance. However, when the surface area is high (paste 16), the series resistance of the device increases significantly, indicating that the barrier layer is too thick and becomes more resistive under test conditions.
[0312] Example 10. Effect of copper particle surface area on etching and fill factor
[0313] This embodiment illustrates the effect of the surface area of copper-containing particles used in the paste on the etchability of the paste. Both the second oxide particles and nanoparticles are capable of etching the silicon nitride (SiN) antireflective coating. It is assumed that the paste's ability to etch through the SiN layer decreases as the surface area contribution of the copper-containing particles increases. The surface area contribution from the copper-containing particles is altered by changing the ratio of coarse to fine copper-containing powder in the paste. Table 7 lists the effect of changing this ratio on the surface area contribution of the copper-containing powder and its effect on the bulk resistivity, contact resistivity, and flyback effect (FF) of the device. The pastes listed in Table 7 include nanoparticles with a Cu / Ni / Pb composition. Theoretically, during firing, the nanoparticles (Cu / Ni / Pb nanoparticles) and Sb₂O₃ second oxide particles melt and coat the surface of the copper-containing particles. Therefore, the greater the surface area contribution of the copper-containing particles, the smaller the proportion of nanoparticles reaching the battery surface and the proportion of second oxide particles from the second oxide particles. All samples were fired using the refractory brick method. The refractory brick method is a technique that places the sample battery on a hot plate set to 300°C for 3 minutes. The sample cells were then immediately transferred to a muffle furnace set to 750°C to 800°C for 1 to 3 seconds. Refractory bricks were stacked on top of the furnace to maintain heat while the furnace door was open. The sample cells were placed directly on the surface of the refractory bricks, and the door remained closed during the time the samples were in the furnace.
[0314] Table 7
[0315]
[0316] The etching process is controlled by the amount of lead (Pb) in the paste, which can be introduced into the paste via nanoparticles (e.g., Ni / Ni / Pb nanoparticles). The molar ratio of Ni:Pb used for synthesis is 14:1. This amount of lead is suitable for a paste containing 0.83 μm...2 The amount of copper / gram paste is sufficient for etching through SiN. x Layers were formed to create a working cell. Using fine (1.2 μm to 3.2 μm) copper-containing powder instead of coarse copper sheets yielded a layer containing 2.73 μm... 2 The paste contains copper per gram. Therefore, it is considered necessary to increase the amount of lead in the paste to etch through SiN. x One solution is to increase the loading of Ni / Ni / Pb nanoparticles in the paste. For this 3.3-fold increase in copper surface area, the molar ratio of Pb to Cu (Pb / (Pb+Cu)) needs to increase by 12-fold. Increasing the amount of nanoparticles in the paste is considered impractical due to the potential negative impact on the printability of the paste. Furthermore, the volume of copper-containing particles in the printed contacts decreases, affecting the resistivity ρ. Therefore, the synthesis of Ni / Ni / Pb nanoparticles was improved (Ni:Pb = 1.6:1) to include a higher proportion of Pb. Subsequently, the amount of nanoparticles in the paste increased by only about 2.5-fold.
[0317] Although the paste containing 100% fine (1.2μm to 3.2μm) copper powder is etched through SiN x But the battery's ρ c It is still high (0.426Ωcm) 2 ). High ρ c The main reason is that cracking in the paste affects the measured resistance. It is believed that the cracking is due to shrinkage caused by densification. To solve this problem, coarse copper sheets are used in the paste. The total surface area of copper in the paste is maintained at 2.73 m². 2 The amount of copper per gram of paste, and the amounts of nanoparticles and secondary oxide (Sb₂O₃) particles remain constant. The amounts of binder and solvent in the organic carrier are adjusted based on the proportion of solids in the paste.
[0318] Figure 18A , Figure 18B and Figure 18C The effect of the ratio of coarse (10 μm to 20 μm) copper to fine (1.2 μm to 3.2 μm) copper on the surface area, volume, and weight contributions of copper-containing materials with nickel is shown. This ratio also affects the bulk resistivity (ρ) and contact resistivity (ρ0). c The impact of ) such as Figure 19A and Figure 19B As shown. Figure 18D and Figure 18EImages of sintered pastes using 100% fine copper powder and 100% coarse copper powder are shown separately. Due to the densification process that occurs during firing, the paste containing only fine copper powder results in the formation of large cracks. As the amount of coarse copper flakes increases, cracking in the fingers decreases. This is due to the ability to load more copper particles into the paste, thereby increasing the volume of copper without increasing the total surface area contribution from copper. When using a 70:30 ratio of coarse to fine copper powder, 3.68 × 10⁻⁶ is achieved. -5 The ρ value of Ωcm.
[0319] Example 11. Effect of the shape of copper-containing particles on the rheological properties and formulation of paste
[0320] This embodiment illustrates the effect of the shape of coarse copper powder on the rheology, microstructure, and formulation of the paste. In this embodiment, the effect of coarse spherical particles is compared with that of coarse flake particles. The shape and packing of the spherical copper-containing particles allow the nanoparticles and second oxide particles (Sb₂O₃) to melt and flow into SiN much faster than the interconnected porous structure of coarse copper flakes. x Layer. Therefore, the amount of nanoparticles and second oxide particles can be reduced; thus, even if the paste contains a high proportion of fine copper-containing particles, a paste containing spherical particles can still have a higher solids loading and a relatively lower viscosity. PV properties, viscosity, and microstructure are shown in [Figure / Table / Illustration]. Figure 20A and Figure 20B , Figure 20C ,as well as Figure 20D and Figure 20E Further research on the composition of the second oxide revealed that ρ c Reduced to 0.065Ωcm 2 .
[0321] Table 8
[0322]
[0323] Table 8 compares paste 4 and paste 17. Figure 20A , Figure 20B and Figure 20C The IV properties of the pastes were compared for the following: (a) a 90:10 mixture of coarse (10 μm to 22 μm) copper powder and fine (1.2 μm to 3.6 μm) copper powder, and (b) a 70:30 mixture of spherical (10 μm to 22 μm) copper powder and fine (1.2 μm to 3.6 μm) copper powder. Cell measurements were performed using a halogen lamp. A comparison of the volume percentage and viscosity of the pastes using coarse (10 μm to 20 μm) copper flakes and (10 μm to 22 μm) spherical copper powder is shown. Figure 20D and Figure 20E The image shows SEM images of sintered fingers from (d) coarse powder and (e) large spherical powder, respectively.
[0324] Example 12. Stacking Study of Copper-Containing Particles of Different Shapes
[0325] To print fingers with the lowest possible resistivity, it is desirable for the particles in the paste to be packed as tightly as possible with minimal void space. The shape and size of the particles, as well as the amount of organic carrier in the paste, will determine how tightly the powder will pack. Table 9 provides estimates of the apparent tap density for different particles used in the paste. Smaller particle sizes or larger particle surface areas result in lower packing density.
[0326] Table 9
[0327]
[0328]
[0329] Table 10
[0330]
[0331] Table 10 shows the ratios of different powders used in the selected pastes. Figure 21A , Figure 21B and Figure 21C Images of square objects printed using the following pastes are shown: (a) paste 18, (b) paste 19, and (c) paste 20. The print detaches from the silicon substrate due to densification and shrinkage. The square objects are placed in a lightbox to observe the porosity of the fired prints. Square objects printed with a higher proportion of fine powder produce a denser structure.
[0332] Figure 22 This is a SEM cross-sectional image of the fingers printed using the paste specified in Table 10 (above). Figure 22 In the above, the pastes are (a) paste 2, (b) paste 5, (c) paste 41, (d) paste 1, (e) paste 21, (f) paste 22, (g) paste 23, (h) paste 24 and (i) paste 25. For pastes containing a higher proportion of fine powder and a wide particle size range, a denser cross-section is obtained.
[0333] Table 11 (below) shows Table 10 and Figure 22 (b) shows the complete paste composition of paste 5. Table 12 shows the complete paste composition of paste 5 as shown in Table 10. Figure 22(d) shows the complete paste composition of paste 1. Paste 1 was formulated such that it contained the same ratio of second oxide particles to nanoparticles to copper-containing particles as the paste used in paste 5. However, to produce a denser cross-section, four different sizes of copper powder (Cu112SP, 610, 603, and C1-2000) were used. It was assumed that the mixing and grinding process would allow the Cu112SP, 610, and 603Cu powders to pack with a packing factor Φ (random Φ) of 0.639. The combined weight of the Cu112SP, 610, and 603 powders was taken as having 70% by weight of copper powder. C1-2000 was added at 30% by weight (of total copper). The Cu / NP weight ratio was kept constant, where PVP = 0.0164 g PVP / g solids. The microstructure of the fingers printed with paste 1 appeared to be denser than those of paste 5.
[0334] Table 11 – Paste Number: Paste 5
[0335]
[0336] Table 12 – Paste Number: Paste 1
[0337]
[0338] Example 13. Effect of organic binders on oxides in reduced paste and their effect on firing conditions
[0339] Some metals in the paste, especially in nanoparticles and coatings on the surface of copper-containing powders, exist in the form of oxides. Introducing oxides into the electrical contacts of the battery will increase the resistivity of the fingers and reduce the short-circuit current density of the device (J). sc The fill factor (FF) and overall efficiency (η) are also considered. However, oxides are advantageous because their synthesis is simpler and the increased surface area is useful during the etching of the anti-reflective (SiN) layer. These materials must be reduced during firing due to their impact on the overall performance of the solar cell device. Typical techniques for reducing oxides during synthesis include the use of hydrogen reducing agents such as hydrazine, sodium borohydride, etc. Synthesis gases are also common reducing agents, but they require specialized furnaces. Organic carriers such as polyvinylpyrrolidone (PVP) decompose at temperatures exceeding 300°C. This decomposition produces reducing gases capable of reducing metal oxides to metals in the paste. This allows the paste to be fired in air while simultaneously reducing the selected oxides present in the paste. The exemplary pastes described herein can be used in furnaces commonly used in the PV industry.
[0340] Figure 23 The X-ray diffraction (XRD) patterns of films formulated with Cu / Ni / Pb nanoparticles, lead oxide, and PVP are shown. Table 13 below lists... Figure 23The composition of the paste. The deposited film clearly shows strong reflections of cuprous oxide (Cu₂O) and lead oxide (PbO₂). In this case, the film is subjected to a rapid sintering process called Intense Pulsed Light (IPL) treatment (also known as photonic sintering). IPL treatment applies multiple light pulses rapidly and continuously to a given sample. The temperature rise experienced by the film depends on the amount of light applied and is a function of the material's thermal conductivity, specific heat capacity, and density. The initial light pulse is used to decompose the PVP in the film and reduce the metal oxides. Subsequent light pulses sinter and melt the particles into a reinforced film. The rapid heating process combined with the PVP in the paste allows the sample to be heat-treated in air. Figure 23 The film after IPL treatment is also shown. The intensity of oxide reflection has been reduced and replaced by strong copper reflection, with the film preferentially oriented towards the Cu(111) peak position. In addition, nickel is also present.
[0341] Table 13
[0342]
[0343] Figure 24A and Figure 24B An example of the effect of the binder on the etching function of the paste is shown. The paste was formulated using Cu / Ni / Pb nanoparticles and a second oxide nanoparticle (antimony oxide). The amount of organic binder (PVP) in the paste was adjusted to change the weight percentage from 1.01 wt% to 3.02 wt%. The composition of the paste can be found in Table 14 below. The paste was printed on monocrystalline silicon solar cells with all-Al BSF back contacts. All cells were fired at 690°C for 3 seconds using the refractory brick method. Figure 24A and Figure 24B The IV curves of the battery measured in the dark are shown. The low current under forward bias indicates that the paste has not etched through the SiN layer and formed an electrical contact with silicon. The relatively high current from 0V to 0.5V indicates that the paste has etched too deeply. When the amount of PVP in the paste is low (1.11 wt%), the reducing gas is insufficient to reduce all oxides (nanoparticles and second oxides) in the paste and etch through the SiN coating. This results in more resistive IV characteristics. As the amount of PVP in the paste increases to 3.02 wt%, the reducing environment caused by PVP decomposition is sufficient to reduce the oxides and etch through the SiN. Figure 24A and Figure 24BThe effect of firing temperature on the ability of PVP to etch through the antireflective coating was also shown. Cells were printed with a paste containing 3.02 wt% PVP and fired using the refractory brick method. The cells were held in the furnace for 3 seconds. Furnace temperatures ranged from 630°C to 720°C. At lower temperatures, the energy input was insufficient to adequately etch through SiN and sinter the copper-containing particles. Above the higher temperatures (720°C), an increase in dark current was observed, indicating that the contact material appeared to have penetrated deeper into the emitter. These results suggest that firing conditions can be tuned by varying the amount of PVP in the paste.
[0344] Table 14
[0345]
[0346] Figures 31A to 31D An example of the role of PVP in a paste is provided. In this embodiment, by changing the surface area of the fine copper-containing particles in the paste (e.g., 1.10 μm...). 2 / g, 2.65m 2 / g and 4.14m 2 The surface area contribution (i.e., the amount of nickel particles coated) from copper-containing particles with nickel was varied by using a 1.10 m² / g ratio. The effect of the amount of organic binder (PVP) on these different paste compositions was also investigated. Table 15 below lists the results using 1.10 m² / g. 2 The paste composition consists of a paste made of fine copper-containing particles per gram and varying amounts (e.g., 1.5 wt%, 2.0 wt%, 2.5 wt%, and 3.0 wt%) of PVP. The effects of the wt% of PVP and the surface area of the fine (1.2 μm to 3.6 μm) copper-containing particles in the paste on the electrical and PV performance of monocrystalline silicon solar cells are investigated. Figure 31A , Figure 31F and Figure 31K -J sc ; Figure 31B , Figure 31G and Figure 31L -V oc ; Figure 31C , Figure 31H and Figure 31M –FF; Figure 31D , Figure 31I and Figure 31N –η; and Figure 31E , Figure 31J and Figure 31O – The total resistance of the entire finger is shown in Figure 24. The paste composition uses materials with a surface area of 1.10 m². 2 / g, 2.65m 2 / g and 4.14m 2 The paste 31 listed in Table 14 ( / g fine copper powder) Figures 31A to 31E ), paste 32 ( Figures 31F to 31J ) and paste 33 ( Figures 31K to 31O The battery was fired using the procedure described in Example 16 at a stage speed of 2.5 cm / s and a setpoint temperature of 753°C in Zone 2. The holding time in Zone 2 ranged from 4 to 8 seconds.
[0347] Figures 31A to 31O This shows the effect on low surface areas (e.g., 1.01 m²). 2 A small amount (e.g., 1.5 wt%) of PVP is sufficient to reduce the oxides in the paste and etch through the SiN layer. Results also indicate that the holding time in region 2 or the setpoint temperature of region 2 can be further reduced to improve the PV performance of the device. Increasing the amount of PVP in these pastes leads to a decrease in performance due to the increased series resistance. Using pastes with a high surface area (e.g., 4.14 m²) is recommended. 2 A paste containing copper powder (g) requires a higher proportion of PVP, a longer holding time, and / or a higher temperature to etch the SiN coating and form a cell.
[0348] Table 15
[0349]
[0350] *Using different batches of fine copper powder to change the surface area of the fine copper powder to produce paste 31, paste 32 and paste 33.
[0351] To produce pastes with different viscosities, the amount of propylene glycol is adjusted.
[0352] Example 14. Effects of second oxide particles and nanoparticles on the electrical properties of paste
[0353] In this embodiment, the bulk resistivity (ρ) and contact resistivity (ρ) of the second oxide particles (e.g., Sb₂O₃) and nanoparticles (e.g., Cu / Ni / Pb) are illustrated. c The effect of antimony (Sb) on silicon. Antimony (Sb) is a known n-type dopant for silicon and is introduced as a potential agent for forming n-type dopants beneath the contact. +The approach to the region, and thus reduce contact resistivity. In this embodiment, commercially available antimony oxide with a particle size range of 1.1 μm to 1.8 μm is used. Antimony oxide has a low melting point (656 °C) and is located just below nickel oxide (NiO) on the Ellingham diagram. Therefore, it requires a similar energy input to be reduced to its elemental form. Furthermore, its location means that antimony can reduce oxides of other elements (Ni, Cu, Pb) in the paste, resulting in a more conductive contact. Antimony oxide was introduced into the paste using a factorial design experimental approach. In this case, the oxide is considered as part of the glass frit system (in addition to Cu / Ni / Pb nanoparticles) that chemically reacts with the SiN layer. The amount of glass frit in the paste is kept constant, and the ratio of nanoparticles to second oxide particles is set at a predetermined "high" or "low" value for both components within 2. 2 Variations were made in the design matrix. This resulted in four possible paste combinations, which were mixed, screen-printed onto monocrystalline silicon solar cells, and fired in air at 690°C for 3 seconds (using the refractory brick method). The effects of using high and low amounts of secondary oxide particles in the paste on bulk resistivity, contact resistance, and the PV performance of the device were investigated. Tables 16, 17, and 18 (below) list the paste compositions used for the design matrix.
[0354] Figure 25A , Figure 25B , Figure 25C , Figure 25D , Figure 25E and Figure 25F This explains the explanation based on 2 2 Factor design matrix alters the level of Cu / Ni / Pb nanoparticles and Sb2O3 particles in the paste, affecting the bulk resistivity ρ( Figure 25A ), contact resistivity ρ c ( Figure 25B ), short-circuit current density J sc ( Figure 25C ), fill factor FF ( Figure 25D ), Open circuit voltage V oc ( Figure 25E ) and efficiency η( Figure 25F The influence and interaction of ).
[0355] The introduction of a second oxide into the paste has a significant impact on both volume resistivity and contact resistivity, and therefore a significant impact on the overall PV performance of the paste. A cross-sectional SEM image (not shown) reveals improved connectivity between copper particles, but a large degree of porosity remains in the film.
[0356] Table 16
[0357]
[0358] Table 17
[0359]
[0360] Table 18
[0361]
[0362] Example 15. Second oxide particles acting as liquid sintering agent
[0363] The fingers are expected to have a denser microstructure to reduce the resistivity of the contacts and thus the series resistance of the device. Second oxide particles (e.g., antimony oxide particles) act as liquid sintering aids due to their relatively low melting point (656°C for Sb₂O₃). A higher proportion of second oxide particles in the paste results in lower sintering temperatures and / or a faster sintering process, as well as densification of the contacts.
[0364] Table 19 shows the composition of paste 38, which uses a 70:30 blend of coarse copper particles and fine copper particles (similar to the blend of paste 5). The amount of second oxide particles is increased to approximately 22% by weight. Figure 26A and Figure 26B As shown, although the copper-containing particles appear to be denser, large voids exist in the microstructure, causing the copper contacts to delaminate from the silicon substrate. Examination of the delaminated contacts using a lightbox revealed that the contacts still possess a significant amount of porosity.
[0365] Table 19 - Paste Number: Paste 38
[0366]
[0367] To further densify the contact material without causing delamination and voids in the microstructure, the copper-containing particles need to be packed as tightly as possible and have a larger volume percentage in the contact material. To increase the density of the contact material, the packing density of the copper-containing particles was studied using the spherical powder shown in Table 8 (above) of Example 11. Calculations were performed assuming the powder had a maximum packing factor of 0.639 and that smaller spherical powder occupies the free space between larger copper particles. Once this value was calculated, the finest (1.2 μm to 3.2 μm) copper powder was added at 30% by weight of the copper powder in the paste. These calculations yielded the following copper-containing particle blends: 37% by weight (10 μm to 22 μm), 21% by weight (7.5 μm to 14.7 μm), 12% by weight (1.8 μm to 7.7 μm), and 30% by weight (1.2 μm to 3.2 μm). Figure 22 (d) shows an example of a cross-section of a contact printed with a blend of this particle size. Although the contact still exhibits a high degree of porosity, the increased number of interparticle connections appears to have reduced the pore size.
[0368] The effect of the second oxide particles as a liquid sintering aid was investigated by increasing the volume percentage of oxide particles in a paste containing blends of four copper-containing powders with different particle sizes. The composition of the paste is shown in Table 20.
[0369] Table 20
[0370]
[0371] Figure 27A , Figure 27B and Figure 27C The effect of increasing the amount of second oxide particles from (a) 4.98 wt% (paste 1) to (b) 8.49 wt% (paste 40) and (c) 12.16 wt% (paste 39) on the microstructure is shown. The larger the volume of the second oxide in the contact, the denser the microstructure. However, as the copper-containing particles form a denser contact, the structure shrinks, and capillary forces push the second oxide out of the narrow pores. Due to this densification and shrinkage, the print detaches from the silicon substrate. Square objects were placed on a lightbox to observe the porosity in the fired print. Contacts printed with pastes containing 8.49 wt% and 12.16 wt% antimony oxide resulted in the contact failing to adhere to the silicon cell. Pools of antimony oxide (and nanoparticles) that had been reduced to their metallic form during the firing process can also be observed at the bottom of the contact; see [link to relevant documentation]. Figure 28A and Figure 28B .
[0372] exist Figure 28A and Figure 28B The image shows a photograph of a square object printed with paste 39, in which... Figure 28A The front of the sample is shown. Figure 28B The back side of the sample is shown. Due to densification and shrinkage, the print detached from the silicon substrate. A square object was placed on a lightbox to observe the porosity in the fired print.
[0373] Example 16. Effects of second oxide particles and nanoparticles on paste etching function and firing conditions
[0374] This embodiment illustrates the role of the second oxide particles and nanoparticles in the etching function of the paste. The total surface area contribution of the copper-containing particles used in the paste is fixed at 0.74 μm. 2 / gram of paste. Use the following settings to print and burn the paste.
[0375] The batteries are fired in a semi-automatic furnace. The system consists of a one-meter-long quartz tube with a volume of approximately 2.4L. The furnace is constructed along the length of the quartz tube into a low-temperature zone (Zone 1) and a high-temperature zone (Zone 2). Compressed air is introduced from the starting point of Zone 1 at a flow rate of 1L / min. The batteries are placed on a nickel-chromium alloy mesh workbench, which is automated using stepper motors and Arduino software to control the speed of battery movement. (Based on T = 38.74S) -1 The speed S is inversely proportional to the time T required for the battery to move from region 1 to region 2. The setpoint temperatures for regions 1 and 2 are 150°C and 753°C, respectively. During the firing process, the battery is placed on a nickel-chromium alloy mesh and moved to region 1 at speed S, where it remains for 180 seconds. The battery then moves to region 2 at speed S and remains there for time t. 保持 The worktable was then moved back to the starting point at a speed of 32.4 cm / s. This allowed the worktable to return to the starting point in less than 2 seconds. The battery was then removed from the worktable and rapidly cooled to room temperature by placing it on a metal plate.
[0376] Figure 29A , Figure 29B , Figure 29C , Figure 29D and Figure 29E The current-voltage (IV) performance of the pastes from Table 21 is shown; these were fired using the method described above. The holding time in region 2 ranged from 1 to 5 seconds. The paste without the second oxide (paste 9) was able to etch through the SiN layer with a holding time of less than 1 second. However, this paste etched too deeply, resulting in lower PV performance. Adding a small amount of second oxide particles (e.g., antimony oxide) to the paste (paste 10) acted as a barrier layer for the nanoparticles, thus slowing down the etching performed by the nanoparticles. Therefore, a holding time of 3 seconds was required before the paste etched through the SiN layer and formed a good electrical contact with the cell. Further increasing the amount of the second oxide (pastes 11, 12, and 13) resulted in a holding time reduced to 2 seconds. The second oxide also acted as an etchant. However, unlike the nanoparticle material, the molten material of the second oxide appeared to wet and etch the SiN layer more uniformly during the firing process. It is believed that a smaller proportion of nanoparticles is needed to etch through the SiN coating and to allow for a higher volume of copper in the fingers. The firing conditions can be controlled by changing the ratio of nanoparticles to second oxide particles in the paste.
[0377] Table 21
[0378]
[0379] Example 17. Effect of the surface area of nickel-containing copper particles on the etching function and firing conditions of the paste.
[0380] This embodiment illustrates the effect of copper-containing particles on the etching and firing conditions of the paste. Table 6 shows the composition of the paste used in this embodiment. All pastes used an antimony oxide secondary oxide particle to nanoparticle (Ni / Ni / Pb) ratio of 1.50. The proportion of nickel nanoparticles in the coating surrounding the copper particles was quantified by the surface area of the coated copper powder.
[0381] To change the proportion of nickel nanoparticles in the paste, the surface area of the fine copper-containing particles in the paste was altered. This was achieved by using a surface area of 1.13 m². 2 / g, 2.61m 2 / g and 25.63m 2 / g of different batches of copper powder were blended to produce a product containing 0.74m 2 Copper particles per gram of paste (paste 11), 0.83 m 2 Copper particles per gram of paste (paste 14), 1.01 m 2 Copper particles / gram paste (paste 15) and 1.10m 2 This is achieved using a paste containing copper particles per gram of paste (paste 16).
[0382] The samples were fired using the firing process described in Example 16. Cells were fired at a stage speed of 1.43 cm / s using Region 2 temperatures of 753°C, 778°C, and 803°C. Table 22 (below) shows the time required to hold the cell in Region 2 to etch through the SiN layer and make contact to produce an FF > 0.6. As shown, the required time increases with increasing copper particle surface area. When using the highest Region 2 temperature (i.e., 803°C), the nickel particles on the copper particles no longer help to slow down the etching process and actually cause the cell to overheat.
[0383] Table 22
[0384]
[0385] Example 18. Effect of firing duration on performance during accelerated aging test
[0386] This embodiment illustrates the impact of firing conditions under accelerated aging on the durability of the battery. This paste is used to metallize a monocrystalline silicon solar cell with an all-Al BSF back contact. The paste shown in Table 6 (Paste 15) uses a total of 1.01 m³ per gram of paste. 2 The cells contained copper particles with nickel. The cells were fired using the process described in Example 16, with a stage speed of 1.43 cm / s and a zone 2 temperature of 753°C. The time the cells were held in zone 2 varied. Figures 30F to 30HExemplary examples of IV curves for the battery at 753°C for 4 seconds, 5 seconds, and 6 seconds are shown. Thermal stress was applied to the battery at 200°C for up to 200 hours, and the PV performance of the device during the test is also shown. Figures 30A to 30E Unbound by theory, this study proposes that nanoparticles form electrical pathways through the glassy interface and also create "spikes" on the silicon surface. Results demonstrate the effect of increasing firing duration on battery life, with batteries exhibiting improved lifespan after longer firing times.
[0387] Example 19: Ratio of Second Oxide to Nanoparticles
[0388] The second oxide particles, nanoparticles, and particles from the coated copper-containing particles in the paste form a liquid sintering aid during the firing process, resulting in a denser contact material for the fingers. The nanoparticles contain lead oxide / hydroxide, which lowers the melting point of the mixture when combined with other materials. When the organic material burns off, droplets of the liquid sintering aid can be expelled from the entire battery surface. These droplets can introduce undesirable aesthetic defects onto the battery surface. It is believed that surface defects hinder the number of photons reaching the active region of the battery, thereby reducing power output. The amount of droplets appearing on the surface can be controlled by changing the ratio of the second oxide to the nanoparticles (Figures 32(a) to (f)). In Figures 32(a) to (f), the following applies: optical microscope images of the fingers after firing. The mass of the paste used for printing the fingers is approximately 1 / 16 (4 × 4 cm) of the paste. 2 (a) 4 mg for the battery (64 mg for a full battery). The fingers in the remaining images were printed using a paste (paste 42) without nanoparticles. The fingers in the remaining images were printed using a second oxide to nanoparticle ratio of (b) 16.75 (paste 43), (c) 8.37 (paste 44), (d) 5.58 (paste 45), (e) 4.19 (paste 46), and (f) 3.35 (paste 47). Table 23 (below) shows the composition of the pastes prepared without nanoparticles and with second oxide to nanoparticle ratios of 16.75, 8.37, 5.58, 4.19, and 3.35.
[0389] Table 23
[0390]
[0391] The amount of paste used for printing fingers directly affects the maximum usable ratio of secondary oxide particles to nanoparticles; fingers using less paste can tolerate a relatively small ratio before this aesthetic imperfection becomes a problem. However, using a higher paste ratio requires a higher total proportion of glass frit (i.e., the combined secondary oxide and nanoparticles), because the secondary oxide is a weaker etchant than the nanoparticles. As the finger width (W) dimension decreases (see...), the ratio of glass frit to nanoparticles increases. Figure 6 The amount of etchant per unit area decreases. Therefore, as the finger width decreases, this ratio can be further reduced. Example 16 (Table 21) shows a paste with a ratio of 0.50. Table 21 also shows a paste containing only nanoparticles and no second oxide particles, while Table 23 shows a paste containing only second oxide particles and no nanoparticles.
[0392] Example 20: Effect of finger size on paste composition
[0393] This embodiment illustrates the effect of finger size on the paste composition. Finger size can be reduced by decreasing the number of prints, resulting in a lower finger height. The height and width of the fingers can also be altered by reducing the pattern size, mesh size, and emulsion thickness used on the screen during the screen printing process.
[0394] Reducing the height of the fingers decreases the amount of paste on the battery. This lowers the proportion of nanoparticles and second oxide particles available per unit area. At some point, the amount of these materials is insufficient to etch through the anti-reflective coating. The etching rate of the combined nanoparticles and second oxide particles is reduced by the particles coated on the copper-containing particles. The more particles in the paste, the more nanoparticles and second oxide particles are needed. However, as the proportion of these materials increases, the bulk resistivity gradually increases. The amount of particles in the paste is limited by the surface area of the coated copper-containing particles.
[0395] The power generated by a solar cell depends on the number of photons of light reaching the cell. Therefore, the larger the area covered by the conductor, the fewer photons reach the cell and the lower the power output. To reduce the size of the fingers, thereby reducing the amount of paste used to print the fingers without affecting device performance, it is necessary to reduce the surface area of the copper-containing particles per gram of paste. To reduce the finger width, the pattern opening size on the screen is reduced. Since the theoretical maximum particle size should be at least 2.5 times smaller than the mesh opening, it is also necessary to reduce the average particle size. Copper-containing particles have the largest particle size in the paste. Therefore, reducing the particle size distribution range of this material naturally leads to an increase in the amount of coating in the paste. When the particle size range of coarse copper-containing particles in the paste is reduced from 10 μm to 22 μm to 7.5 μm to 14.7 μm, the proportion of binder in the paste increases because the larger surface area makes the powder more susceptible to oxidation during the firing process. The paste is printed onto a polycrystalline silicon solar cell and fired using the same semi-automatic furnace described in Example 16. Figures 33(a) and 33(b) illustrate the effect of increasing the amount of glass frit and the surface area contribution of copper-containing particles on the amount of paste required to maintain the fill factor of the device. In Figures 33(a) and 33(b), the following applies: the effect of increasing the amount of glass frit in the paste on PV performance (fill factor, FF) as the contribution of the used surface area is (a) 0.80 m². 2 / gram of paste and (b) 0.57m 2 The printing weight of the paste made from copper-containing powder is a function of the paste weight per gram. The battery was fired using a table speed of 1.43 cm / s, zone 1 temperature of 192°C, zone 2 temperature of 820°C, airflow of 5 L / min, and zone 2 holding time of 5 seconds. The battery was fired in a 4×4 cm... 2 Seventeen 100 μm wide fingers were printed on the polycrystalline silicon solar cell. The composition of the paste is shown in Table 24 (below). The paste uses a secondary oxide to nanoparticle ratio of approximately 16.75. The results show that the surface area contribution of the copper-containing particles is increased from approximately 0.80 μm. 2 / gram of paste reduced to approximately 0.57m 2 / gram of paste can reduce the mass of paste required for printing finger-shaped objects. This is achieved by reducing the surface area of the fine copper powder in the paste from 2.41m². 2 / g decreased to 1.61m 2 The surface area contribution of the copper-containing particles is controlled by the number of prints (i.e., 3 prints). This reduction in surface area allows for the use of a double-print method to achieve similar performance.
[0396] Table 24
[0397]
[0398] By reducing the surface area of fine copper powder to 1.15m² 2 / g, the screen printing process is reduced to a single print; therefore, the total surface area contribution from copper-containing particles is 0.40m². 2 / gram of paste. Use 0.40m 2 Full-size polycrystalline Si cells were printed using a paste of 16.70 to 16.75 wt% and a secondary oxide to nanoparticle ratio of 16.70 to 16.75. The binder content in the paste was increased from 1.69 wt% to 2.32 wt%. Cells were fired in a TP Solar Model M-225 (Neutrino series) IR belt furnace. This furnace contained six heating zones and one cooling zone, which was approximately 30% longer than the total length of the heating zones. These zones were designed so that the front and back of the cells were simultaneously heated using IR heating lamps. The temperatures of zones 1 through 5 were 620°C, 460°C, 440°C, 450°C, and 520°C, respectively. Zone 6 ranged from 665°C to 690°C. Belt speeds ranged from 225 inches / minute to 400 inches / minute. Cells were cut into 4×4cm pieces. 2 The sample was used to measure PV performance. Figure 34A , Figure 34B , Figure 34C and Figure 34D The effect of firing conditions on the PV performance of full-size cells cut into small pieces is shown. For Figures 34A to 34D The following applies: PV performance ((a) short-circuit current density, (b) open-circuit voltage, (c) fill factor, and (d) efficiency) as a function of the belt speed used for firing cells in an industrial IR belt furnace. The temperature in zones 1 through 5 of the furnace remained unchanged. The temperature in zone 6 was increased from 665°C to 690°C. Two versions of CuBert, containing 1.69 wt% binder (paste 54) and 2.32 wt% binder (paste 55), were printed on full-size polycrystalline silicon cells. TM Paste. The battery is printed in a single printing process. After firing, the battery is cut into 4×4cm pieces. 2 The portion was measured. (Shown) Figures 34A to 34D The results shown illustrate the average results for 1 / 8 to 1 / 4 full-size cells. The composition of the paste is shown in Table 25.
[0399] Table 25
[0400]
[0401] By reducing the size of the screen openings, the width and quality of the paste used for printing fingers can be further reduced. To achieve this, only copper-containing particles with a size range of 1.20 μm to 3.20 μm are used in the paste. Figure 35 The result shows a surface area contribution of 0.51m.2 The effect of copper-containing particles on the paste (Paste 56 - see table below) per gram. The paste used a 3.35 ratio of secondary oxide to nanoparticles and a binder concentration of 3.28 wt%. As a result, the paste was used in 1 / 16 (4 × 4 cm) 2 The mass of the paste used to print the fingers on the portion was reduced to approximately 6 mg (approximately 96 mg for a full-size cell). The paste was printed onto a single-crystal passivated emitter rear contact (PERC) silicon solar cell and fired using a modified version of the semi-automatic furnace described in Example 16. In this case, three separate tube furnaces were combined into a system, with a single 122 cm long quartz tube passing through all three furnaces: thus creating a three-zone furnace. The airflow through the system was controlled by an exhaust outlet located at either end of the quartz tube. The cell was placed on a nichrome wire workbench, which was automated using stepper motors and Arduino software to control the speed at which the cell passed through each zone. The speed at which the cell passed through different zones was varied to simulate the belt speed used in the TP Solar IR six-zone belt furnace. The cell moved continuously through the different zones until it reached the end of the quartz tube, where a fan was turned on to rapidly cool the cell back to room temperature. The cell was then removed from the workbench. Figure 35 The IV curves of batteries fired at temperatures in regions 1, 2, and 3 (255°C, 505°C, and 990°C, respectively) are shown. Figure 35 The following applies: Current-voltage (IV) profiles of a paste (Paste 56) made using only fine 1.2 μm to 3.2 μm copper-containing powder under both dark and light conditions. This paste was printed onto monocrystalline silicon PERC cells and fired using a three-zone semi-automatic furnace. The temperatures in zones 1, 2, and 3 were 255 °C, 505 °C, and 990 °C, respectively. The cells were fired at a belt speed of 325 inches per minute.
[0402] Reducing the surface area contribution of smaller copper-containing particles 46 can further limit the charge speed at which batteries can be fired. Figure 36A , Figure 36B and Figure 36C This shows the effect of using 0.51m. 2 / gram of paste, 0.57m 2 / gram of paste and 0.65m 2 The surface area of the paste contributes to the paste's composition, and the firing conditions affect the battery's open-circuit voltage V. oc The paste used a 3.35% secondary oxide to nanoparticle ratio and a binder concentration of 3.28% by weight. The composition of the paste is shown in Table 26 (below). The lower secondary oxide to nanoparticle ratio, combined with a lower surface area, resulted in a significantly reduced V at slower speeds.oc .
[0403] Table 26
[0404]
[0405] The changes in paste composition, surface area contribution, and amount of paste required to produce a device with a fill factor > 0.6 are summarized in Table 27.
[0406] Table 27
[0407]
[0408] Example 21: The effect of controlling etching depth and adhesive on durability
[0409] Figure 37A and Figure 37B The effect of the binder ratio in the paste on battery durability under accelerated aging conditions is shown. Figure 37A and Figure 37B The following is applicable to: accelerated aging tests at 200°C using CuBert. TM The effect of paste metallization on the PV performance ((a) open-circuit voltage, (b) pseudo-fill factor) of polycrystalline silicon cells with all-Al BSF back contacts. Two versions of CuBert were printed on 6-inch polycrystalline Si cells containing 1.69 wt% binder (Paste 54) and 2.32 wt% binder (Paste 55). TM Paste. The results below show 4×4cm cuts from full-size cells fired in an IR belt furnace at 665°C, Zone 6 temperature, and 300 inches per minute (BS). 2 The average results are shown in the graphs. The graphs also show the results for samples fired using a zone 6 temperature of 690°C and a belt speed (BS) of 325 inches / minute. Polycrystalline cells were printed using a paste containing 1.69 wt% and 2.36 wt% binder. The composition of the paste is provided in Table 25. Cells were fired using the six-zone TP Solar IR belt furnace described in Example 20. This furnace used zone 1, zone 2, zone 3, zone 4, and zone 5 temperatures of 620°C, 460°C, 440°C, 450°C, and 520°C, respectively. The temperature of zone 6 varied from 665°C to 690°C. The belt speed was varied. Full-size cells were cut into smaller 4×4cm sections. 2 Cells were used to evaluate their PV performance. Accelerated aging tests were performed by heating the cells at 200°C for 1000 hours in an inert atmosphere. Cells were periodically pulled out throughout the testing period to measure their PV performance. Monitoring was conducted using Sinton Instruments Suns-V... oc The system measures the open-circuit voltage V.oc The performance was determined using the pseudo-filling factor pFF (Figure 37). V oc And pFF is sensitive to diffusion of copper into the junction; if this occurs, V is expected to... oc The pFF decreased over time. The results indicate that increasing the proportion of binder in the paste reduces the depth of paste etching into the battery, thereby increasing battery durability.
[0410] Example 22: The Influence of Nanoparticle Composition
[0411] Nanoparticles and second oxide particles provide the etching capability of the paste. The etching rate can be altered by changing the ratio of these two materials in the paste. It can also be altered by changing the composition of the nanoparticles. As mentioned above, the invasiveness of the nanoparticles can be controlled by changing the ratio of different elements during the synthesis of the nanoparticles. In this embodiment, the molar ratio of nickel (Ni) to lead (Pb) in the Ni / Ni / Pb nanoparticles is reduced from 1.52 to 0.52 during synthesis. The paste, using this two-nanoparticle composition, is fabricated and printed onto a monocrystalline silicon PERC cell. The cell is fired in a three-zone semi-automatic firing system described in Example 20. The temperatures in zones 1, 2, and 3 are 650°C, 450°C, and 925°C, respectively. Figure 38A and Figure 38B The effect of these nanoparticles on PV performance is shown. Figure 38A and Figure 38B The following applies: the efficiency of monocrystalline silicon PERC solar cells printed using pastes made from standard Ni / Ni / Pb nanoparticles, where the Ni / Pb ratio is 1.52 (pastes 55 and 57) and where the ratio is 0.52 (pastes 56 and 58). The figure also shows the effect of doubling the proportion of nanoparticles and the amount of binder on PV performance. The composition of the pastes is shown in Table 28.
[0412] Table 28
[0413]
[0414] Example 23: The effect of copper particle size on firing conditions
[0415] Reducing finger size requires not only altering the paste composition but also changing the firing conditions. Smaller copper particles are more prone to oxidation. Increasing the proportion of binder and etchant in the paste helps reduce any oxides and those formed during firing. However, these two components can only be increased to a certain level before affecting device performance. Therefore, firing conditions need to be changed. The battery was fired using the three-zone semi-automatic firing system described in Example 20. In the first two zones, most of the binder was burned off, but due to the small finger size, the proportion of binder remaining was already small. Therefore, the temperature in the first zone was lowered to address this effect. Figure 39A , Figure 39B and Figure 39C The effect of decreased temperature in region 1 and increased binder content in the paste on the lateral resistance of the fingers is shown. Table 29 shows the composition of the paste. The cell is in a 4×4 cm... 2 Approximately 3.5 mg of paste is printed on the monocrystalline silicon PERC cell. Figure 39A , Figure 39B and Figure 39C The following applies: the effect of firing conditions on the resistivity of all 22 fingers, each 3.2 mm in length, printed using a paste containing (a) 2.05 (paste 59), (b) 2.35 (paste 60), and (c) 2.64 (paste 61) wt% binder. The fingers are 4 × 4 cm. 2 The paste was printed on the monocrystalline silicon PERC cell using approximately 3.5 mg of paste.
[0416] Table 29
[0417]
[0418] Example 24: Increasing screen life for pastes with smaller finger sizes
[0419] Reducing the particle size in the paste may lead to a decrease in the life of the screen used in the paste, as the increased surface area increases the drying rate of the paste. Replacing the solvent used in the medium directly with a solvent with a lower evaporation rate can extend the screen life. Table 30 shows the physical properties of the solvents tested in the paste.
[0420] Table 30
[0421]
[0422] Example 25: Finger Size
[0423] Table 31 shows the average dimensions of a high-viscosity paste (paste 53) printed using a 300-mesh screen with an emulsion over mesh (EOM) coating of 20 μm mesh openings and 100 μm wide finger openings. The cells were fired using a TPSolar six-zone IR belt furnace, with zones 1, 2, 3, 4, 5, and 6 at temperatures of 620°C, 460°C, 440°C, 450°C, 520°C, and 840°C, respectively. For both unfired and fired fingers, the average width and height of the fingers were measured from cross-sectional images using optical and scanning electron microscopy, respectively. Figure 40 A cross-sectional image of the fired fingers is shown. The reduction in size is due to the densification of the internal structure. A cross-sectional SEM image of the fingers (printed with paste 53) fired using a TP solar six-zone IR belt furnace is shown. Figure 40 middle.
[0424] Table 31
[0425]
[0426] The printing width can be further reduced by adjusting the screen (for example, see...). Figure 4 (W2 in the table). Reducing the finger openings and increasing the mesh count to a higher number results in smaller openings, thus reducing the amount of paste passing through the screen. Typically, a screen opening smaller than the target finger width is used. In other words, the print width is usually wider than the corresponding screen opening size. Reducing the diameter of the filaments in the mesh and the EOM (Extended Osmotic Membrane) decreases the thickness of the deposit. These changes, along with changes in print speed, are common modifications made to achieve the desired results. Table 32 and... Figure 41A and Figure 41B The effect of screen parameters on the printing width of relatively low viscosity paste is shown. Figure 41A and Figure 41B The image shows a 360-mesh wire mesh with 60μm wide finger openings (see [reference]). Figure 41A ) and a 400-mesh wire mesh with 35μm wide finger openings (see Figure 41B An optical microscope image of the paste (paste 63) after printing.
[0427] Table 32
[0428]
[0429] Although the invention has been illustrated by way of example through the description of several embodiments, and although these embodiments have been described in detail, the inventors do not intend to limit the scope of the appended claims to or in any way restrict it to such details. Therefore, other advantages and modifications will be apparent to those skilled in the art. Various features of the invention may be used alone or in any combination, depending on the user's needs and preferences.
[0430] 1. A paste for metallizing solar cells, the paste comprising:
[0431] Organic carriers, and
[0432] The organic carrier contains a mixture of copper-containing particles, metal-oxide-containing nanoparticles, and second oxide particles different from the metal-oxide-containing nanoparticles.
[0433] The second oxide particles include particles of metal oxide, and when the paste is heated to the temperature at which the organic carrier decomposes, the metal of the metal oxide is capable of reducing at least some of the metal-oxide-containing nanoparticles to metal.
[0434] 2. The paste of claim 1, wherein the organic carrier is capable of reducing the metal oxide of the second oxide particles via decomposition of the organic carrier.
[0435] 3. The paste of claim 1, wherein the organic carrier comprises polyvinylpyrrolidone.
[0436] 4. The paste of claim 1, wherein the second oxide particles comprise glass frit particles.
[0437] 5. The paste as claimed in claim 1, wherein the copper-containing particles comprise metallic copper particles or copper alloy particles.
[0438] 6. The paste of claim 5, wherein the copper particles have at least one metal selected from nickel, cobalt, or manganese on the surface of the copper particles or on the surface of the copper alloy particles.
[0439] 7. The paste of claim 6, wherein at least one metal selected from nickel, cobalt, or manganese is in the form of metal particles on the surface of the copper particles or on the surface of the copper alloy particles.
[0440] 8. The paste of claim 6, wherein at least one metal selected from nickel, cobalt, or manganese is in the form of metal oxide particles on the surface of the copper particles or on the surface of the copper alloy particles.
[0441] 9. The paste of claim 6, wherein the copper particles or the copper alloy particles and / or the at least one metal are doped with at least phosphorus.
[0442] 10. The paste of claim 6, wherein the surface of the copper particles or the surface of the copper alloy particles is not completely covered by the at least one metal.
[0443] 11. The paste of claim 6, wherein the at least one metal covers at least a portion of the surface of the copper particles or at least a portion of the surface of the copper alloy particles.
[0444] 12. The paste of claim 1, wherein the metal oxide of the second oxide particles is an antimony oxide.
[0445] 13. The paste of claim 1, wherein the metal-oxide-containing nanoparticles comprise at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.
[0446] 14. The paste of claim 1, wherein the metal-oxide-containing nanoparticles include nickel oxide and lead oxide.
[0447] 15. The paste of claim 14, wherein the metal oxide of the second oxide particles comprises antimony oxide.
[0448] 16. The paste of claim 1, wherein the metal-oxide-containing nanoparticles include nickel oxide, copper oxide, and lead oxide.
[0449] 17. The paste of claim 1, wherein the paste is silver-free.
[0450] 18. The paste of claim 1, wherein the ratio of the second oxide particles to the metal-oxide-containing nanoparticles is in the range of 0.50 to 16.96 by weight.
[0451] 19. The paste of claim 1, wherein the ratio of the second oxide particles to the metal-oxide-containing nanoparticles is in the range of 1.50 to 3.51 by weight.
[0452] 20. The paste of claim 1, wherein at least one metal selected from nickel, cobalt, and manganese is in the form of metal particles on the surface of the copper-containing particles, and the surface area of the copper-containing particles having the metal particles is 1m². 2 / g to 5m 2 Within the range of / g.
[0453] 21. The paste of claim 1, wherein the copper-containing particles comprise a mixture of fine copper powder and coarse copper powder.
[0454] 22. The paste of claim 21, wherein the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm, and the coarse copper powder is characterized by an average particle size in the range of 7.53 μm to 14.69 μm, 10 μm to 20 μm, or 1.75 μm to 7.20 μm.
[0455] 23. The paste of claim 1, wherein the organic carrier is an organic binder and an organic solvent.
[0456] 24. The paste of claim 23, wherein the organic carrier further comprises a viscosity modifier.
[0457] 25. The paste of claim 23, wherein the organic solvent is propylene glycol.
[0458] 26. The paste of claim 23, wherein the organic carrier further comprises an organic binder.
[0459] 27. A paste comprising:
[0460] Organic carriers, and
[0461] The mixture of particles in the organic carrier, the mixture of particles comprising copper particles, nanoparticles and metal oxide particles,
[0462] The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide, and lead oxide.
[0463] 28. The paste of claim 27, wherein the metal oxide of the metal oxide particles has a more negative Gibbs free energy of formation than the metal oxide of at least one oxide in the nanoparticles.
[0464] 29. The paste of claim 27, wherein the copper particles occupy the largest volume portion of the metal in the paste.
[0465] 30. The paste of claim 27, wherein the nanoparticles comprise particles containing lead oxide.
[0466] 31. The paste of claim 27, wherein the nanoparticles are nickel oxide and lead oxide.
[0467] 32. The paste of claim 27, wherein the metal oxide particles comprise particles of antimony oxide.
[0468] 33. The paste of claim 27, wherein the nanoparticles comprise particles containing lead oxide and the metal oxide particles comprise particles containing antimony oxide.
[0469] 34. The paste of claim 27, wherein the organic carrier is capable of reducing the metal oxide particles via decomposition of the organic carrier.
[0470] 35. The paste of claim 27, wherein the organic carrier comprises polyvinylpyrrolidone.
[0471] 36. The paste of claim 27, wherein the metal oxide particles comprise glass frit particles.
[0472] 37. The paste of claim 27, wherein the copper particles have at least one metal selected from nickel, cobalt, or manganese on their surface.
[0473] 38. The paste of claim 37, wherein at least one metal selected from nickel, cobalt, or manganese is in the form of metal particles on the surface of the copper particles.
[0474] 39. The paste of claim 37, wherein at least one metal selected from nickel, cobalt, or manganese is in the form of metal oxide particles on the surface of the copper particles.
[0475] 40. The paste of claim 37, wherein the copper particles and / or the at least one metal are doped with at least phosphorus.
[0476] 41. The paste of claim 37, wherein the surface of the copper particles is not completely covered by the at least one metal.
[0477] 42. The paste of claim 37, wherein the at least one metal covers at least a portion of the surface of the copper particles.
[0478] 43. The paste of claim 37, wherein the metal oxide particles are particles of antimony oxide.
[0479] 44. The paste of claim 37, wherein the nanoparticles comprise at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide.
[0480] 45. The paste of claim 37, wherein the nanoparticles comprise nickel oxide and lead oxide.
[0481] 46. The paste of claim 45, wherein the metal oxide particles are particles of antimony oxide.
[0482] 47. The paste of claim 37, wherein the nanoparticles comprise nickel oxide, copper oxide, and lead oxide.
[0483] 48. The paste of claim 27, wherein the paste is silver-free.
[0484] 49. The paste of claim 27, wherein the ratio of metal oxide particles to nanoparticles is in the range of 0.5 to 17 by weight.
[0485] 50. The paste of claim 27, wherein the ratio of metal oxide particles to nanoparticles is in the range of 1.5 to 3.5 by weight.
[0486] 51. The paste of claim 27, wherein the copper particles are modified to include metal-containing particles on the surface of the copper particles.
[0487] 52. The paste of claim 51, wherein the surface area of the modified copper particles is greater than the surface area of the unmodified copper particles.
[0488] 53. The paste of claim 51, wherein the surface area of the modified copper particles is 1m². 2 / g to 5m 2 Within the range of / g.
[0489] 54. The paste of claim 27, wherein the copper particles comprise a mixture of fine copper powder and coarse copper powder.
[0490] 55. The paste of claim 54, wherein the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm, and the coarse copper powder is characterized by an average particle size in the range of 7.53 μm to 14.69 μm, 10 μm to 20 μm, or 1.75 μm to 7.20 μm.
[0491] 56. The paste of claim 27, wherein the organic carrier is an organic binder and an organic solvent.
[0492] 57. The paste of claim 56, wherein the organic carrier further comprises a viscosity modifier.
[0493] 58. The paste of claim 56, wherein the organic solvent is propylene glycol.
[0494] 59. The paste of claim 56, wherein the organic carrier further comprises an organic binder.
[0495] 60. A paste that is essentially composed of the following:
[0496] Organic carriers, and
[0497] The organic carrier contains a mixture of copper particles, nanoparticles, and metal oxide particles.
[0498] The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide, and lead oxide.
[0499] 61. A paste comprising the following:
[0500] Organic carriers, and
[0501] The organic carrier contains a mixture of copper particles, nanoparticles, and metal oxide particles.
[0502] The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, antimony oxide, tellurium oxide, bismuth oxide, and lead oxide.
[0503] 62. A solar cell, comprising:
[0504] Semiconductor substrate; and
[0505] At least one copper-containing conductor on the semiconductor substrate,
[0506] The copper-containing conductor comprises a plurality of grains of copper or copper alloy, and at least a portion of the grain boundaries between adjacent grains comprises at least one of lead, copper, cobalt, manganese, tellurium and bismuth and at least one other metal.
[0507] 63. The solar cell of claim 62, wherein the oxide of at least one other metal has a more negative Gibbs free energy of formation than the lead oxide.
[0508] 64. The solar cell of claim 62, wherein the at least one other metal is antimony.
[0509] 65. The solar cell of claim 62, wherein at least a portion of the grain boundaries further comprises nickel.
[0510] 66. The solar cell of claim 62, wherein the copper-containing conductor and the semiconductor substrate meet at an interface, and the interface comprises lead and the at least one other metal between the semiconductor substrate and the grain.
[0511] 67. The solar cell of claim 66, wherein the interface comprises a metal silicide.
[0512] 68. The solar cell of claim 66, wherein the interface further comprises nickel.
[0513] 69. The solar cell of claim 62, wherein the solar cell does not contain silver.
[0514] 70. The solar cell of claim 62, wherein the copper-containing conductor is a finger.
[0515] 71. The solar cell of claim 70, wherein the thickness of the fingers is in the range of 10 μm to 100 μm.
[0516] 72. The solar cell of claim 70, wherein the solar cell comprises a highly doped silicon emitter layer and the fingers are in electrical contact with the silicon emitter layer.
[0517] 73. The solar cell of claim 70, wherein the resistivity of the fingers is in the range of 2 to 10 times that of bulk copper.
[0518] 74. The solar cell of claim 62, wherein the conductor is a bus.
[0519] 75. The solar cell of claim 74, wherein the thickness of the busbar is in the range of 10 μm to 100 μm.
[0520] 76. The solar cell of claim 74, wherein the solar cell includes an antireflective layer on the semiconductor substrate, the antireflective layer defining an outer surface of the solar cell, and the busbar is in direct contact with the antireflective layer but not with the semiconductor substrate.
[0521] 77. The solar cell of claim 62, wherein the solar cell further comprises a plurality of buses arranged in a pattern in which the buses are spaced apart at a distance of less than 40 mm.
[0522] 78. The solar cell of claim 62, wherein the solar cell has no separately deposited diffusion barrier layer between the copper conductor and the semiconductor substrate.
[0523] 79. A method for manufacturing a solar cell, comprising:
[0524] The paste is placed on the surface of the substrate, the paste comprising:
[0525] Organic carriers, and
[0526] The mixture of particles in the organic carrier, the mixture of particles comprising copper particles, nanoparticles and metal oxide particles,
[0527] The nanoparticles include at least one of nickel oxide, copper oxide, cobalt oxide, manganese oxide, and lead oxide; and
[0528] The paste is heated to a temperature at which the organic carrier decomposes and at least some of the metal oxides are reduced to metal.
[0529] 80. The method of claim 79, wherein heating comprises heating in air.
[0530] 81. The method of claim 79, wherein during heating, the metal reduces at least some of the metal-oxide-containing nanoparticles to metal.
[0531] 82. The method of claim 81, wherein the substrate comprises a silicon nitride layer, and during heating, a heated metal oxide and a metal react with the silicon nitride layer.
[0532] 83. A method for modifying the surface of copper-containing particles for use in pastes, the method comprising:
[0533] Mix copper-containing particles with metal ions in a solution;
[0534] A reducing agent is added to a mixture of copper-containing particles and metal ions to reduce the metal ions to metal, causing the metal to deposit on the surface of the copper-containing particles; and
[0535] Surface-modified copper-containing particles were separated from the solution.
[0536] 84. The method of claim 83, further comprising:
[0537] A mixture containing copper particles, metal ions, and a reducing agent is heated.
[0538] 85. The method of claim 83, wherein the surface area of the surface-modified copper particles is greater than that of the copper particles before the metal was deposited.
[0539] 86. The method of claim 83, wherein the surface-modified copper-containing particles have a surface area of at least 0.83 m². 2 / g.
[0540] 87. The method of claim 83, wherein the metal ion is one or more of nickel, manganese, and cobalt.
[0541] 88. A paste comprising the surface-modified copper-containing particles as described in claim 83.
[0542] 89. A method for preparing a paste for metallizing solar cells, comprising:
[0543] A plurality of particles are mixed together in an organic carrier, wherein the plurality of particles include copper-containing particles, nanoparticles, and second oxide particles.
[0544] 90. The method of claim 89, wherein prior to mixing, the method further comprises:
[0545] The surface of the copper-containing particles is modified to increase the surface area of the copper-containing particles by 1.5% to 20%.
[0546] 91. The method of claim 89, wherein prior to mixing, the method further comprises:
[0547] The surface of the copper-containing particles is modified by exposing the copper-containing particles to a solution and depositing particles of metal and / or metal oxides on the surface of the copper-containing particles.
[0548] 92. The method of claim 89, wherein prior to mixing, the method further comprises:
[0549] A first powder containing the copper-containing particles is mixed with a second powder containing the copper-containing particles. The first powder is characterized by a first average particle size and a first particle size distribution, and the second powder is characterized by a second average particle size and a second particle size distribution, wherein the first average particle size is greater than the second average particle size.
[0550] 93. The method of claim 89, wherein the mixing comprises mixing at least 80% by weight of the copper-containing particles, 1% to 15% by weight of the second oxide particles and 1% to 10% by weight of the nanoparticles with 1% to 13% by weight of the organic carrier.
[0551] 94. The method of claim 89, wherein mixing comprises mixing copper particles, nanoparticles containing at least lead, and antimony oxide particles together.
[0552] 95. The paste of claim 1, wherein the copper-containing particles are composed of fine copper powder.
[0553] 96. The paste of claim 95, wherein the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm.
[0554] 97. The paste of claim 1, wherein the ratio of the second oxide particles to the metal-oxide-containing nanoparticles is in the range of 0.25 to 20 by weight.
[0555] 98. The paste of claim 1, wherein the ratio of the second oxide particles to the metal-oxide-containing nanoparticles is in the range of 3 to 17 by weight.
[0556] 99. The paste of claim 1, wherein at least one metal selected from nickel, cobalt, and manganese is in the form of metal particles on the surface of the copper-containing particles, and the surface area of the copper-containing particles having the metal particles is 0.7 m². 2 / g to 5m 2 Within the range of / g.
[0557] 100. The paste of claim 27, wherein the nanoparticles comprise lead hydroxide particles and the metal oxide particles comprise antimony oxide particles.
[0558] 101. The paste of claim 56, wherein the organic solvent is one or a combination of propylene glycol, dipropylene glycol, and tripropylene glycol.
[0559] 102. The method of claim 83, wherein the surface-modified copper-containing particles have a surface area of at least 0.66 m². 2 / g.
[0560] 103. The method of claim 89, wherein prior to mixing, the method further comprises:
[0561] The surface of the copper-containing particles is modified to increase the surface area of the copper-containing particles by at least 1.5%.
[0562] 104. The paste of claim 27, wherein the ratio of metal oxide particles to nanoparticles is in the range of 0.25 to 20 by weight.
[0563] 105. The paste of claim 27, wherein the ratio of metal oxide particles to nanoparticles is in the range of 3 to 17 by weight.
[0564] 106. The paste of claim 51, wherein the surface area of the modified copper particles is 0.7 m². 2 / g to 5m 2 Within the range of / g.
[0565] 107. The paste of claim 27, wherein the copper particles are composed of fine copper powder.
[0566] 108. The paste of claim 107, wherein the fine copper powder is characterized by an average particle size in the range of 1.2 μm to 3.2 μm.
[0567] 109. The paste of claim 33, wherein the nanoparticles further include lead hydroxide-containing particles.
Claims
1. A solar cell comprising: Semiconductor substrate; and at least one copper-containing conductor on said semiconductor substrate, The copper-containing conductor includes a plurality of grains of copper or a copper alloy, and at least a portion of grain boundaries between adjacent grains contain at least one of lead, copper, cobalt, manganese, tellurium and bismuth and at least one other metal.
2. The solar cell of claim 1, wherein the oxide of at least one other metal has a more negative Gibbs free energy of formation than lead oxide.
3. The solar cell of claim 1, wherein the at least one other metal is antimony. The solar cell according to claim 1 , wherein at least a portion of the grain boundaries further comprise nickel.
5. The solar cell of claim 1, wherein the copper-containing conductor and the semiconductor substrate meet at an interface, and the interface comprises lead and the at least one other metal between the semiconductor substrate and the grains.
6. The solar cell of claim 5, wherein the interface comprises a metal silicide.
7. The solar cell of claim 5, wherein the interface further comprises nickel.
8. The solar cell of claim 1, wherein the solar cell is free of silver.
9. The solar cell of claim 1, wherein the copper-containing conductor is a finger. 10 . The solar cell of claim 9 , wherein the thickness of the fingers is in the range of 10 μm to 100 μm.